Soil indicators and changes in organic matter under organic, natural, and conventional coffee production in the Brazilian Atlantic Forest - Victória Alvarenga Rios; Vanessa Maria de Souza Barros; Hugo Felipe da Silva; Jônatas Pedro da Silva; Humberto Josué de Oliveira Ramos; Eric Batista Ferreira; Teogenes Senna de Oliveira (Agriculture, Ecosystems & Environment, 2026)

Long-Term Genomic Surveillance Unveils Key Drivers of Salmonella Contamination and Antimicrobial Resistance Dynamics in Surface Waters from Central Mexico - Enrique Jesús Delgado-Suárez; Santiago Zapata-Ramírez; Luz del Carmen Sierra-Gómez Pedroso; Francisco Alejandro Ruíz-López; Nayarit Emérita Ballesteros-Nova; Orbelín Soberanis-Ramos; María Salud Rubio-Lozano; Luisa María Sánchez-Zamorano; Yaselda Chavarin-Pineda; Rebecca Bell; Anna Brover; Maria Balkey; et al. (Water, Air, & Soil Pollution, 2026)

Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Brevetoxin biosynthesis in Karenia brevis in relation to light, growth phase, and across the cell cycle - Charles L. Tilney; Alicia E. Hoeglund; Eric Muhlbach; Leanne Flewelling; Maria Célia Villac; Dana M. Nieuwkerk; Sugandha Shankar; John H. Paul; Katherine A. Hubbard (Harmful Algae, 2026)

Longitudinal blood pressure changes in relation to urinary toxic/essential metals and metal mixtures - Margaret C. Weiss; Jiehuan Sun; Brian P. Jackson; Mary E. Turyk; Luyu Wang; Eric L. Brown; David Aguilar; Sharon A. Brown; Craig L. Hanis; Maria Argos; Robert M. Sargis (Environmental Research, 2026)

Minimum mortality temperature by cause of death and age group: A multi-country observational study (1990–2019) - Seunghyun Eom; Aurelio Tobias; Masahiro Hashizume; Daewon Yang; Claire Demoury; Eric Lavigne; Aleš Urban; Klea Katsouyanni; Francesco Sera; Paul Lester Carlos Chua; Susana das Neves Pereira da Silva; Dominic Royé; et al. (Environmental Research, 2026)

Comparison of seafood intake estimates and biomarkers for assessing impact on child cognition and behavior - Mariza Kampouri; Mia Stråvik; Sven Bölte; Eric Zander; Klara Gustin; Michael Levi; Agnes E. Wold; Anna Sandin; Malin Barman; Ann-Sofie Sandberg; Maria Kippler; Marie Vahter (Environmental Research, 2026)

Normative assessment of corneal thickness and iridocorneal angle parameters in guinea pigs (Cavia porcellus) using spectral-domain optical coherence tomography - Fábio L. C. Brito; Maria F. X. Rocha; Jéssica N. Voitena; Eric C. Ledbetter; Fabiano Montiani-Ferreira (Veterinary Research Communications, 2026)

Basal release of 6-cyanodopamine from rabbit isolated aorta and its modulation of vascular reactivity - Eric Xavier Dos Santos; Kashif Ali; José Britto-Júnior; Larryn Peterson; Joshua J. L. Morris; Alex Miller; Felipe Fernandes Jacintho; Maria Elisabete Moraes; Vincenzo Santagada; Giuseppe Caliendo; Beatrice Severino; Edson Antunes; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
6-Cyanodopamine (6-CYD) is a recently identified endogenous catecholamine that exerts positive chronotropic and inotropic actions, but its occurrence in vascular tissue and effects on vascular reactivity are unknown. In endothelium-intact and endothelium-denuded rabbit isolated aortic rings, we investigated the basal release of 6-CYD and its effects on aortic smooth muscle reactivity. 6-Cyanodopamine release was quantified by LC–MS/MS. Isometric tension was recorded to assess concentration–response curves to noradrenaline, adrenaline, and dopamine in aortic rings pre-incubated or not with 6-CYD, whereas vasorelaxation was evaluated in endothelin-1 (ET-1)-pre-contracted rings. Rabbit aorta released significant amounts of 6-CYD, which were largely reduced either by endothelium removal or pre-incubation with the NOX1/4 inhibitor GKT137831 (1 µM), whereas the nitric oxide (NO) synthase inhibitor L-NAME (100 µM) and the voltage-gated sodium channel blocker tetrodotoxin (TTX, 1 µM) had no significant effect. Addition of 6-CYD (0.1 pM to 10 nM) had no contractile activity itself, but it significantly potentiated noradrenaline- and adrenaline-induced aortic contractions, an effect largely reduced by endothelium removal. The dopamine-induced aortic contractions remained unaffected by 6-CYD. In ET-1-pre-contracted rings, 6-CYD (1 nM–10 µM) produced concentration-dependent relaxations that were significantly reduced by endothelium removal and L-NAME (100 µM), as well as by the soluble guanylyl cyclase (sGC) inhibitors ODQ (100 µM) and methylene blue (10 µM). In conclusion, these findings identify vascular endothelium as a source of 6-CYD and indicate this catecholamine as a novel endogenous modulator of vascular tone, acting through a dual mechanism, namely, potentiating vasoconstriction and producing NO/sGC-dependent vasorelaxation.

Association between air temperature and COVID-19 emergency department visits in Ontario, Canada: A population-based case-crossover study - Nicholas Grubic; Erjia Ge; Zhou Zang; Eric Lavigne; Michael A. Campitelli; Haley Golding; Tariq Cisse; Maria Koh; Brice Batomen; Jane Liu; Xiaolin Wei (International Journal of Hygiene and Environmental Health, 2026)

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Survival at a cost: Corals endure microplastic and nanoplastic pollution by sacrificing energy reserves - Kiara Lange; Christine Ferrier-Pagès; Léna Canestrier; Cécile Rottier Henry; Maria-Isabelle Marcus Do Noscimiento; Eric Béraud (Marine Pollution Bulletin, 2026)

Photocatalytic performance of CuAl layered double hydroxide nanocomposites with AuPd bimetallic particles and cyclodextrins for dye degradation and nitro reduction under sunlight - Luiz Phelipe S. Tomaso; Maria Eduarda A. Rocha; Gabriel Francisco S. da Silva; Luis Henrique Lacerda; Suellen D.T. de Barros; Marcelo E.H. Maia da Costa; Suzana B. Peripolli; José Brant de Campos; Sébastien Noël; Stéphane Menuel; Eric Monflier; Anne Ponchel; et al. (Applied Clay Science, 2026)

Short-term laboratory assessment of elevated temperature effects on two aquatic plants - Joanna Rosińska; Eric Puche; Maria A. Rodrigo (Aquatic Ecology, 2026)

The Green Transition will be just – Or it won't succeed - Barbara Prainsack; Maria Patrão Neves; Nils-Eric Sahlin; Nikola Biller-Andorno; Jeroen van den Hoven; Migle Laukyte; Paweł Łuków; Fruzsina Molnar-Gabor; Thérèse Murphy; Tamar Sharon; Takis Vidalis; Mihalis Kritikos (Environmental Science & Policy, 2026)

Title: The evaluation of ruminal undegradable protein supplementation level on growth performance and ovarian development in beef heifers grazing native rangelands. - Taylor N. Andrews; Maria K. Chavez; Emily A. Melchior; Collin Anderson; Alexis B. Tamez; Shelby L. Rosasco; Shad H. Cox; Richard L. Dunlap; Robert A. Cushman; Jennifer A. Hernandez-Gifford; Eric J. Scholljegerdes; Adam F. Summers (Animal Reproduction Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Assessing the Influence of Agricultural Injuries on the Welfare of Cocoa Farming Households in Ghana - Enoch Kwame Tham-Agyekum; Gifty-Maria Sangber-Dery; Fred Ankuyi; John-Eudes Andivi Bakang; Stephen John Ayeh; Eric Nfaaful (Journal of Agromedicine, 2026)

Estimation of aboveground biomass in Atlantic Forest fragments using hyperspectral-RPA data: assessing the effect of spatial resolution and shadowed pixels - Nívea Maria Mafra Rodrigues; Gilson Fernandes da Silva; Catherine Torres de Almeida; Fabio Guimarães Gonçalves; Rorai Pereira Martins-Neto; Eric Bastos Görgens; Emanuel Maretto Effgen; Tobias Baruc Moreira Pinon; André Quintão de Almeida (International Journal of Remote Sensing, 2026)

Low-dose Intestinal Exposure to Botulinum Neurotoxins Increases Susceptibility to Salmonella and Shigella Infection - Federico Fabris; Paola Brun; Aram Megighian; Giulia Bernabè; Ignazio Castagliuolo; Ilenia Drigo; Luca Bano; Florigio Lista; Maria Lina Bernardini; Eric A. Johnson; Cesare Montecucco; Ornella Rossetto (Toxicon, 2026)

Assessment of space weather modeling capabilities and transition to operations - Maria M. Kuznetsova; Martin A. Reiss; Edmund Henley; Eric Adamson; Suzy Bingham; Mario M. Bisi; François-Xavier Bocquet; Laura Boucheron; Min-Yang Chou; Claudio Corti; Gian Luca Delzanno; Richard A. Fallows; et al. (Advances in Space Research, 2026)

The SCEPTRE Suction Device: Bridging Portability and Performance in Combat Medicine - Eric L. Wiatrek; Maria J. Londono; Saketh R. Peri; Connor J. Evans; Robert A. De Lorenzo; R. Lyle Hood (Annals of Biomedical Engineering, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Sediment routing and palaeogeographic evolution of the Western Alpine Foreland Basin during the early collisional stage - Bastien Huet; Eric Lasseur; Nicolas Bellahsen; Justine Briais; Nicolas Loget; Jean-Pierre Suc; Jean-Loup Rubino; Matthias Bernet; Speranta-Maria Popescu (Earth-Science Reviews, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The role of hydrogen sulfide and trisulfur radical ion in molybdenum transport by hydrothermal fluids: implications for porphyry-epithermal Cu-Au-Mo deposits - Maria A. Kokh; Gleb S. Pokrovski; Stephan Klemme; Christian Schmidt; Clément Laskar; Jean-Louis Hazemann; Denis Testemale; Isabelle Kieffer; Olivier Proux; Eric Lahera; Harald Müller; Elena F. Bazarkina; et al. (Geochimica et Cosmochimica Acta, 2026)

Decoding butyrate fermentation with glucose as a model substrate: Parameter optimization and metagenomic insights - Xiaoxiao Shi; Shohei Yasuda; Maria Tuohy; Zhongzhong Wang; Yuansheng Hu; Eric Trably; Piet N.L. Lens; Xinmin Zhan (Bioresource Technology, 2026)

Changes in soil organic matter in intercropped coffee systems and their effects on soil enzymatic and microbial activity - Siro Paulo Moreira; Vanessa Maria de Souza Barros; David Gabriel Campos Pereira; Hugo Felipe da Silva; Humberto Josué de Oliveira Ramos; Eric Batista Ferreira; Teogenes Senna de Oliveira (Applied Soil Ecology, 2026)

Essential dietary fatty acids affect intraspecific competition in herbivorous zooplankton - Maja Ilić; Sina Brehm; Maria Stockenreiter; Eric von Elert; Patrick Fink (Limnology and Oceanography, 2026)
The trophic transfer efficiency at the pelagic phytoplankton‐zooplankton interface is—among other factors—governed by the dietary availability of polyunsaturated fatty acids (PUFAs) to herbivorous zooplankton. As most zooplankton taxa cannot synthesize PUFAs de novo, the phytoplankton PUFA composition is crucial for the herbivores' fitness. As PUFA synthesis is taxon‐specific in phytoplankton, alterations in phytoplankton biodiversity lead to changes in the phytoplankton trait “nutritional quality” and can thus be expected to affect the relative fitness and intraspecific competition of herbivore populations. To study this potentially important link between producer diversity and consumer competitive interactions, we performed a freshwater mesocosm experiment with diversity‐manipulated natural phytoplankton communities and naturally coexisting Daphnia longispina genotypes. We found that phytoplankton diversity is correlated with its PUFA composition, suggesting that a biodiversity loss on the primary producer level leads to decreased PUFA diversity and ultimately reduced dietary quality for consumers. This change in dietary PUFA availability further affected competitive interactions between co‐occurring D. longispina genotypes, which was most evident for the ω3‐PUFA α‐linolenic acid (18:3 n‐3) and the ω6‐PUFA arachidonic acid (20:4 n‐6). Interestingly, these two PUFAs had opposite effects on competition by favoring different genotypes. Our study thus demonstrates that phytoplankton PUFA content is a trait that affects consumers' functional traits and therefore represents a potential link between biodiversity and competition in aquatic herbivores.

Mapping forest successional stages with UAVs: comparing RGB and multispectral imagery in seasonal tropical forests - Adéliton da Fonseca De Oliveira; Huezer Viganô Sperandio; Maria Luiza de Azevedo; Artur Ferro de Souza; Israel Marinho Pereira; Luciano Cavalcante de Jesus França; Eric Bastos Gorgens (Environmental Monitoring and Assessment, 2025)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Maternal responsiveness to child receptiveness and fullness cues from 8 to 24 months of age and their relation with complementary feeding approach and language proficiency - Alice Di Prete; Guido Maria Caruso; Denise Del Grosso; Eleonora Giacomini; Sara Picuno; Giulia Trappetti; Valentina Focaroli; Melania Paoletti; Giulia Pecora; Barbara Caravale; Corinna Gasparini; Serena Gastaldi; et al. (Appetite, 2025)

Phenylpropanoids and lignans in memp seeds (Cannabis sativa L. semen): identification and quantification - Ilaria Maria Crimi; Pietro Allegrini; Stefania Bosisio; Eric de Combarieu; Nicola Sardone; Francesco Sicolo (Phytochemistry Letters, 2025)

Captive Male and Female West Indian Manatees Display Variable Vocal and Behavioral Responses to Playbacks of Conspecifics - Beth A. Brady; Eric A. Ramos; Jake A. Lasala; Zoe Nadine R. Ferrell; Nicholas A. Kaney; Emerson Martinez; Maria Renee Areolla Illescas; Joe Arena (Marine Mammal Science, 2025)
Manatees exhibit diverse vocalizations in various behavioral contexts, but the exact role of these sounds, particularly in terms of sex‐based distinctions, remains elusive. This study sought to discern the behavioral and vocal responses of two subspecies of captive West Indian manatees ( Trichechus manatus ) to different call types (squeaks and squeals) to determine whether differences are related to the sex of the signaler. In Mexico, four female Antillean manatees ( Trichechus manatus manatus ) were subjected to playbacks, while in Florida, two male Florida manatees ( Trichechus manatus latirostris ) were used for a parallel experiment. Vocal responses were captured using two hydrophones, with an underwater speaker system facilitating the playback. Video footage was collected to observe behavioral changes in response to playback. Results indicated that neither male nor female manatees increased the number of calls, changed call type, or altered acoustic parameters regardless of call type or whether the sound played was male or female. Likewise, neither males nor females significantly altered their behavior or movement towards the speaker in response to male or female calls, or call type. However, individual Antillean manatees exhibited variation in their behavioral responses to playback of conspecific vocalizations. The results suggest that manatees may not distinguish between the sex of callers.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Towards zero waste in pomegranate juice by-products: Biomass valorization beyond phenolic compound recovery and development of bioactive pectin-based edible coatings - Gessica Maria Lopes Faria; Eric Keven Silva (Journal of Cleaner Production, 2025)

Strengthening pathogen and antimicrobial resistance surveillance through environmental monitoring in sub-Saharan Africa: stakeholder perspectives - Ananda Tiwari; Taru Miller; Vito Baraka; Marc Christian Tahita; Vivi Maketa; Bérenger Kaboré; Paul Tunde Kingpriest; Patrick Mitashi; Eric Lyimo; Hillary Sebukoto; Ana Maria de Roda Husman; Tarja Pitkänen (International Journal of Hygiene and Environmental Health, 2025)

Spectro-photometry of Phobos simulants II. Effects of porosity and texture - Antonin Wargnier; Olivier Poch; Giovanni Poggiali; Thomas Gautier; Alain Doressoundiram; Pierre Beck; Tomoki Nakamura; Hideaki Miyamoto; Shingo Kameda; Nathalie Ruscassier; Arnaud Buch; Pedro H. Hasselmann; et al. (Icarus, 2025)

Why is there so much variability in crop multi-model studies? - Daniel Wallach; Taru Palosuo; Henrike Mielenz; Samuel Buis; Peter Thorburn; Senthold Asseng; Benjamin Dumont; Roberto Ferrise; Sebastian Gayler; Afshin Ghahramani; Matthew Tom Harrison; Zvi Hochman; et al. (Agricultural and Forest Meteorology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Harnessing methods, data analysis, and near-real-time wastewater monitoring for enhanced public health response using high throughput sequencing - Padmini Ramachandran; Tunc Kayikcioglu; Tamara Walsky; Kathryn Judy; Jasmine Amirzadegan; Candace Hope Bias; Bereket Tesfaldet; Maria Balkey; Dietrich EppSchmidt; Hugh Rand; James Pettengill; Sandra Tallent; et al. (Environmental Research, 2025)

Distinct neural networks of emotional valence and uncertainty in the human amygdala underlying different mental disorders - Shitong Xiang; Chao Xie; Xiao Xiao; Tobias Banaschewski; Gareth J. Barker; Arun L.W. Bokde; Herta Flor; Antoine Grigis; Hugh Garavan; Penny Gowland; Andreas Heinz; Rüdiger Brühl; et al. (Science Bulletin, 2025)

Evaluating the AgMIP calibration protocol for crop models; case study and new diagnostic tests - Daniel Wallach; Kwang Soo Kim; Shinwoo Hyun; Samuel Buis; Peter Thorburn; Henrike Mielenz; Sabine Julia Seidel; Phillip D. Alderman; Benjamin Dumont; Mohammad Hassan Fallah; Gerrit Hoogenboom; Eric Justes; et al. (European Journal of Agronomy, 2025)

Pig meniscus single-cell sequencing reveals highly active red zone chondrocyte populations involved in stemness maintenance and vascularization development - Monika Mankowska; Monika Stefanska; Anna Maria Mleczko; Katarzyna Sarad; Witold Kot; Lukasz Krych; Julia Anna Semba; Eric Lars-Helge Lindberg; Jakub Dalibor Rybka (Journal of Zhejiang University-SCIENCE B, 2025)
Meniscus injuries are widespread and the available treatments do not offer enough healing potential. Here, we provide critical support for using pigs as a biological model for meniscal degeneration and the development of cutting-edge therapies in orthopedics. We present a single-cell transcriptome atlas of the meniscus, consisting of cell clusters corresponding to four major cell types: chondrocytes, endothelial cells, smooth muscle cells, and immune cells. Five distinct chondrocyte subclusters (CH0–CH4) were annotated, of which only one was widespread in both the red and white zones, indicating a major difference in the cellular makeup of the zones. Subclusters distinct to the white zone appear responsible for cartilage-specific matrix deposition and protection against adverse microenvironmental factors, while those in the red zone exhibit characteristics of mesenchymal stem cells and are more likely to proliferate and migrate. Additionally, they induce remodeling actions in other chondrocyte subclusters and promote the proliferation and maturation of endothelial cells, inducing healing and vascularization processes. Considering that they have substantial remodeling capabilities, these subclusters should be of great interest for tissue engineering studies. We also show that the cellular makeup of the pig meniscus is comparable to that of humans, which supports the use of pigs as a model in orthopedic therapy development.

Assessment climate change impacts on a key species of campos rupestres: can we preserve the everlasting flower? - Maria Luiza de Azevedo; Huezer Viganô Sperandio; Fernanda de Aguiar Coelho; Ricardo Siqueira da Silva; Eric Bastos Gorgens (Plant Ecology, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

Effects of the herbicide bentazone on the structure of plankton and benthic communities representative of Mediterranean coastal wetlands: a mesocosm experiment - Daniel Grillo-Avila; Maria Antón-Pardo; Javier Armengol; Eric Puche; Rafael Carballeira; Jesús Moratalla-López; Jose Francisco Palacios-Abella; Isabel López; Melina Celeste Crettaz Minaglia; Pablo Amador; Carlos Rochera; Antonio Picazo; et al. (Hydrobiologia, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Microbiome and pollutants in the freshwater sponges Ephydatia muelleri (Lieberkühn, 1856) and Spongilla lacustris (Linnaeus, 1758) from the sub-Arctic Pasvik river (Northern Fennoscandia) - Carmen Rizzo; Gabriella Caruso; Giovanna Maimone; Luisa Patrolecco; Marco Termine; Marco Bertolino; Stefania Giannarelli; Alessandro Ciro Rappazzo; Josef Elster; Alessio Lena; Maria Papale; Tanita Pescatore; et al. (Environmental Research, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Predictors of Salmonella enterica contamination in agricultural and livestock-impacted natural watersheds - Alan D.L. Rocha; Laiorayne A. Lima; Gustavo F.C. Sales; Nadyra J. Silva; Maria L.R. Gomes; Walter E. Pereira; Patrícia E.N. Givisiez; Eric W. Brown; Marc W. Allard; Rebecca L. Bell; Magaly Toro; Jianghong Meng; et al. (Environmental Pollution, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Cultural activity and impact of extreme weather events revealed by ambient seismic noise and perspective on quick clay failure monitoring in Oslo, Norway - Charlotte Bruland; Anna Maria Dichiarante; Andreas Köhler; Volker Oye; Ivan Van Bever; Eric Larose (Engineering Geology, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Land suitability modeling integrating geospatial data and artificial intelligence - Huezer Viganô Sperandio; Marcelino Santos de Morais; Luciano Cavalcante de Jesus França; Danielle Piuzana Mucida; Reynaldo Campos Santana; Ricardo Siqueira da Silva; Cristiano Reis Rodrigues; Bruno Lopes de Faria; Maria Luiza de Azevedo; Eric Bastos Gorgens (Agricultural Systems, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Imagine, Discover, Inspire: Proceedings of the 4th International Conference of the Trisomy 21 Research Society - Lisi Flores-Aguilar; Eric D. Hamlett; Paula Araya; Eugenio Barone; Anita Bhattacharyya; Maria Carmona-Iragui; Li Chan; Brad Christian; Alberto C. S. Costa; Floriana Costanzo; Laura Del Hoyo Soriano; Mara Dierssen; et al. (NeuroMolecular Medicine, 2025)
Down syndrome (DS) or trisomy 21 (T21) is present in a significant number of children and adults around the world and is associated with cognitive and medical challenges. Through research, the T21 Research Society (T21RS), established in 2014, unites a worldwide community dedicated to understanding the impact of T21 on biological systems and improving the quality of life of people with DS across the lifespan. T21RS hosts an international conference every two years to support collaboration, dissemination, and information sharing for this goal. In 2022, T21RS hosted an international conference in Long Beach, California, from June 9 to 12. The conference, attended by 483 people including scientists, families, self-advocates, and industry representatives from 17 countries, was a dynamic and interactive meeting that shared discoveries from international research teams. This summary highlights the scientific discoveries shared at the 4th T21RS meeting with the Imagine, Discover, Inspire theme.

Intercropping: ecosystem functioning and sustainable agriculture - Rui-Peng Yu; Dorte B. Dresbøll; Maria R. Finckh; Eric Justes; Wopke van der Werf; Andrew Fletcher; Georg Carlsson; Long Li (Plant and Soil, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Soil Nitrogen Supply Exerts Largest Influence on Leaf Nitrogen in Environments with the Greatest Leaf Nitrogen Demand - Alissar Cheaib; Elizabeth F. Waring; Risa McNellis; Evan A. Perkowski; Jason P. Martina; Eric W. Seabloom; Elizabeth T. Borer; Peter A. Wilfahrt; Ning Dong; Iain Colin Prentice; Ian J. Wright; Sally A. Power; et al. (Ecology Letters, 2025)
Accurately representing the relationships between nitrogen supply and photosynthesis is crucial for reliably predicting carbon–nitrogen cycle coupling in Earth System Models (ESMs). Most ESMs assume positive correlations amongst soil nitrogen supply, leaf nitrogen content, and photosynthetic capacity. However, leaf photosynthetic nitrogen demand may influence the leaf nitrogen response to soil nitrogen supply; thus, responses to nitrogen supply are expected to be the largest in environments where demand is the greatest. Using a nutrient addition experiment replicated across 26 sites spanning four continents, we demonstrated that climate variables were stronger predictors of leaf nitrogen content than soil nutrient supply. Leaf nitrogen increased more strongly with soil nitrogen supply in regions with the highest theoretical leaf nitrogen demand, increasing more in colder and drier environments than warmer and wetter environments. Thus, leaf nitrogen responses to nitrogen supply are primarily influenced by climatic gradients in photosynthetic nitrogen demand, an insight that could improve ESM predictions.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Size-fractionated carbonaceous and iron-rich particulate matter in urban environments of France and Senegal - Laurence Delville; Jean-François Léon; Mélina Macouin; Yann-Philippe Tastevin; François Demory; Arnaud Proietti; Pedro Henrique da Silva Chibane; Maria Dias Alves; Mayoro Gueye; Laure Laffont; Eric Gardrat; Sonia Rousse; et al. (Environmental Science and Pollution Research, 2024)
Road traffic is one of the main sources of particulate matter in the urban environment, emitting particulate organic and elemental carbon compounds and metal-rich particles through combustion and brakes and tires wear. In Western Africa, the carbon and metal composition of airborne particles is also influenced by additional sources linked to biomass combustion and recent industrialization. Here, we investigated the impact of combustion-related and non-combustion-related emissions on the distribution of carbonaceous fractions and iron-rich particles in two urban environments in France and Senegal. The supermicron fraction ( $$D_a>{1}$$ D a > 1 µm) showed a significantly higher isothermal remanent magnetization (SIRM) than finer fractions, accounting for 79% in France and 81% in Senegal of the total SIRM. In the submicron fraction ( $$D_a<{1}$$ D a < 1 µm), we noted significantly higher concentrations of total carbon (TC) and elemental carbon (EC) than for other fractions, both accounting for 71% in France and 68% and 75% in Senegal of the total and elemental particulate carbon concentration, respectively. Electron microscope observations revealed the presence of iron-rich particles for $$D_a<{0.2}$$ D a < 0.2 µm, however, associated with a weak SIRM. Such iron particles may be produced by combustion or abrasion while we suspect that emissions by the abrasion process produce larger particles.

Associations of gestational and childhood exposure to lead, cadmium, and fluoride with cognitive abilities, behavior, and social communication at 4 years of age: NICE birth cohort study - Mariza Kampouri; Eric Zander; Klara Gustin; Anna Sandin; Malin Barman; Ann-Sofie Sandberg; Agnes E. Wold; Sven Bölte; Maria Kippler; Marie Vahter (Environmental Research, 2024)

Blood mercury concentrations in preschool children and potential risk factors in São Paulo, Brazil - Fernanda Junqueira Salles; Elizeu Chiodi Pereira; Allan Santos de Oliveira; Eric A.C. da Costa; Thiago Nogueira; Marcelo de Oliveira Lima; João Paulo Góes Pereira; Thais Karolina Lisboa Queiroz; Brenda Rodrigues Chagas; Iracina Maura de Jesus; Agnes Soares da Silva; Maria Regina Alves Cardoso; et al. (Environmental Pollution, 2024)

Special AT-rich sequence-binding protein 2 immunohistochemistry in the diagnosis of osteosarcoma in dogs - Alba Maria M. Shank; Eric Snook; Kimberly Cavender; Joseph McCoy; Nicolas Sorensen; Bradley Siegrist; Brian Tabb (Journal of Comparative Pathology, 2024)

Model based analysis of trace metal dosing strategies to improve methane yield in anaerobic digestion systems - Susan George; Maria Rosaria Mattei; Luigi Frunzo; Giovanni Esposito; Eric D. van Hullebusch; Fernando G. Fermoso (Bioresource Technology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Spectro-photometry of Phobos simulants - Antonin Wargnier; Thomas Gautier; Alain Doressoundiram; Giovanni Poggiali; Pierre Beck; Olivier Poch; Eric Quirico; Tomoki Nakamura; Hideaki Miyamoto; Shingo Kameda; Pedro H. Hasselmann; Nathalie Ruscassier; et al. (Icarus, 2024)

Characterization and treatment of industrial laundry wastewaters: a review - Grégorio Crini; Dario Lacalamita; Eric Lichtfouse; Nadia Morin-Crini; Chong Liu; Lee D. Wilson; Lorenzo A. Picos-Corrales; Mabel Amen Akhere; Maria Sotiropoulou; Corina Bradu; Chiara Mongioví (Environmental Chemistry Letters, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Population genetic diversity of Cunene horse mackerel Trachurus trecae on the Angolan coast: Implications for management and conservation - Kenneth Gabriel Mota; Caio Augusto Perazza; Filomena Vaz Velho; Maria de Lourdes Sardinha; Letícia Morais; Jussara Oliveira Vaini; Eric Hallerman; Alexandre Wagner Silva Hilsdorf (Fisheries Research, 2024)

The hypertidal Santa Cruz–Chico River estuary (South Patagonia, Argentina): A hybrid ria-type system under extreme tides, arid climate and active uplift - Bernadette Tessier; Jean-Yves Reynaud; Jose I. Cuitiño; Roberto A. Scasso; Léo Pancrazzi; Maria Duperron; Pierre Weill; Viviane Bout-Roumazeilles; Eric Armynot du Châtelet; Anjana Kuinkel; Thibaud Lortie; Laurent Dezileau (Sedimentary Geology, 2024)

Food safety assessment and 28-day toxicity study of the synbiotic medical food consortium SBD121 - D. Davidson Easson; Vincent A. Murphy; Alicia E. Ballok; Maria J. Soto-Giron; Kelsey J. Miller; Mark R. Charbonneau; Eric M. Schott; Tracy Greene; Joseph Rodricks; Gerardo V. Toledo (Food and Chemical Toxicology, 2024)

A calibration protocol for soil-crop models - Daniel Wallach; Samuel Buis; Diana-Maria Seserman; Taru Palosuo; Peter J. Thorburn; Henrike Mielenz; Eric Justes; Kurt-Christian Kersebaum; Benjamin Dumont; Marie Launay; Sabine Julia Seidel (Environmental Modelling & Software, 2024)

Atomic force microscopy characterization of white and beige adipocyte differentiation - Alia Mallah; Katerina Stojkova; Ronald N. Cohen; Nehal Abu-Lail; Eric M. Brey; Maria A. Gonzalez Porras (In Vitro Cellular & Developmental Biology - Animal, 2024)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Pulsed electric field, ultrasound and microwave heating based extraction techniques for valorization of pomegranate peel by-products: A review - Gessica Maria Lopes Faria; Eric Keven Silva (Journal of Environmental Chemical Engineering, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Ecotoxicological strategies employing biochemical markers and organisms to monitor the efficacy of malathion photolysis treatment - Rafaela Imoski; Laís Jarenko da Cruz; Angela Maria Palacio-Cortés; Ana Marta Schafaschek; Eric Schwamberger; Pamella Regina Mariotti; Andre Luis Bichibichi Borges; Fernando Rodrigues-Silva; Liziê Daniela Tentler Prola; Mario Antônio Navarro da Silva; Adriane Martins de Freitas; Marcus Vinicius de Liz (Chemosphere, 2024)

Air quality, metal(loid) sources identification and environmental assessment using (bio)monitoring in the former mining district of Salsigne (Orbiel valley, France) - Aude Calas; Eva Schreck; Jérôme Viers; Astrid Avellan; Alain Pages; Maria Dias-Alves; Eric Gardrat; Philippe Behra; Véronique Pont (Chemosphere, 2024)

Changes in submerged macrophyte diversity, coverage and biomass in a biosphere reserve site after 20 years: A plea for conservation efforts - Eric Puche; Daniel Cruz; Pilar Delgado; Joanna Rosińska; Maria A. Rodrigo (Biological Conservation, 2024)

Petrogenesis of volcanic rocks from the Quaternary Eifel volcanic fields, Germany: detailed insights from combined trace-element and Sr–Nd–Hf–Pb–Os isotope data - Mike W. Jansen; Carsten Münker; Josua J. Pakulla; Eric Hasenstab-Dübeler; Christian S. Marien; Toni Schulz; Maria Kirchenbaur; Kathrin P. Schneider; Robin Tordy; Vera Schmitt; Frank Wombacher (Contributions to Mineralogy and Petrology, 2024)
Quaternary rocks from the East and West Eifel volcanic fields in western Germany are a key suite of intraplate volcanic rocks that can provide insights into volcanism of the Central European Volcanic Province (CEVP) and into continental intraplate volcanism in general. We present a comprehensive dataset for Eifel lavas including isotope as well as major and trace element data for 59 samples covering representative compositions of the different volcanic fields. In line with previous studies, the lavas are all SiO 2 -undersaturated, alkaline-rich and mainly comprise primitive basanites, melilitites, and nephelinites (Mg# ≥ 57). Geochemical compositions of samples from both volcanic subfields display distinct differences in their trace-element as well as radiogenic isotope compositions, largely confirming previous subdivisions. Coupled trace-element and radiogenic Sr–Nd–Hf–Pb–Os isotope compositions can now provide firm evidence for spatially heterogeneous mantle sources and compositionally distinct magmatic pulses. Within the West Eifel Field, Sr–Nd–Pb isotope compositions of the younger (≤80 ka), ONB-suite (olivine-nephelinite-basanite) are similar to FOZO (FOcal ZOne) or the EAR (European Asthenospheric Reservoir) and resemble compositions that have been previously reported from plume-sourced ocean island basalts (OIB). In marked difference, older (700 Ma to 80 ka) volcanic rocks from the F-suite (Foidite) in the West Eifel field and from the entire east Eifel Field tap a more enriched mantle component, as illustrated by more radiogenic Sr isotope ( 86 Sr/ 87 Sr up to 0.705408) and variable Pb isotope compositions ( 206 Pb/ 204 Pb = 18.61–19.70, 207 Pb/ 204 Pb = 15.62–15.67 and 208 Pb/ 204 Pb = 38.89–39.76). Combined trace-element compositions of ONB-suite samples are in good agreement with results from batch melting models suggesting a hybrid composition of Eifel magmas formed through mixing 10% of a FOZO-like melt with 90% of a DMM-like melt, similar to melts from the Tertiary HEVF. However, radiogenic Sr–Nd–Pb isotope compositions of F-suite and EEVF and some ONB lavas require the admixture of melts from lithospheric mantle sources. Elevated Nb/Ta and Lu/Hf ratios in combination with variable 187 Os/ 188 Os ratios can now demonstrate the presence of residual carbonated eclogite components, either in the lithosphere or in the asthenospheric mantle. Finally, by combining geochemical and temporal constraints of Tertiary and Quaternary volcanism it becomes evident that CEVP volcanism in central and western Germany has resulted from compositionally distinct magmatic pulses that tap separate mantle sources. Although the presence of a mantle plume can neither be fully confirmed nor excluded, plume-like melt pulses which partially tap carbonated eclogite domains that interact to variable extents with the lithosphere provide a viable explanation for the temporal and compositional cyclicity of CEVP volcanism.

Microclimate, an important part of ecology and biogeography - Julia Kemppinen; Jonas J. Lembrechts; Koenraad Van Meerbeek; Jofre Carnicer; Nathalie Isabelle Chardon; Paul Kardol; Jonathan Lenoir; Daijun Liu; Ilya Maclean; Jan Pergl; Patrick Saccone; Rebecca A. Senior; et al. (Global Ecology and Biogeography, 2024)
Brief introduction: What are microclimates and why are they important? Microclimate science has developed into a global discipline. Microclimate science is increasingly used to understand and mitigate climate and biodiversity shifts. Here, we provide an overview of the current status of microclimate ecology and biogeography in terrestrial ecosystems, and where this field is heading next. Microclimate investigations in ecology and biogeography We highlight the latest research on interactions between microclimates and organisms, including how microclimates influence individuals, and through them populations, communities and entire ecosystems and their processes. We also briefly discuss recent research on how organisms shape microclimates from the tropics to the poles. Microclimate applications in ecosystem management Microclimates are also important in ecosystem management under climate change. We showcase new research in microclimate management with examples from biodiversity conservation, forestry and urban ecology. We discuss the importance of microrefugia in conservation and how to promote microclimate heterogeneity. Methods for microclimate science We showcase the recent advances in data acquisition, such as novel field sensors and remote sensing methods. We discuss microclimate modelling, mapping and data processing, including accessibility of modelling tools, advantages of mechanistic and statistical modelling and solutions for computational challenges that have pushed the state‐of‐the‐art of the field. What's next? We identify major knowledge gaps that need to be filled for further advancing microclimate investigations, applications and methods. These gaps include spatiotemporal scaling of microclimate data, mismatches between macroclimate and microclimate in predicting responses of organisms to climate change, and the need for more evidence on the outcomes of microclimate management.

Maillard conjugates produced from proteins and prebiotic dietary fibers: Technological properties, health benefits and challenges - Adela Cristina Martinez Urango; Maria Angela A. Meireles; Eric Keven Silva (Trends in Food Science & Technology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Biotic transformation of methylmercury at the onset of the Arctic spring bloom - Stephen G. Kohler; Lars-Eric Heimbürger-Boavida; Philipp Assmy; Oliver Müller; Stefan Thiele; Maria G. Digernes; Kuria Ndungu; Murat V. Ardelan (Progress in Oceanography, 2024)

The impact of probiotic live yeast in a barley grain-based diet on feed efficiency, carcass traits, and immune-oxidative status of artificially reared lambs - Alexandros Mavrommatis; Christos Christodoulou; Panagiota Kyriakaki; Alexis Skourtis; Basiliki Kotsampasi; Vladimiros Christodoulou; George Symeon; Maria Karatzia; Despoina Karatosidi; Soumela Savvidou; Federico Righi; Georgios Arsenos; et al. (Animal Feed Science and Technology, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Experimental and computational fluid-structure interaction analysis and optimization of Deep-V planing-hull grillage panels subject to slamming loads – Part II: Irregular waves - Evan J. Lee; Matteo Diez; Emily L. Harrison; Minyee J. Jiang; Lawrence A. Snyder; Ann Marie R. Powers; Raymond J. Bay; Andrea Serani; Maria L. Nadal; Eric R. Kubina; Frederick Stern (Ocean Engineering, 2024)

Temperature alters the toxicological impacts of plant terpenoids on the polyphagous model herbivore Vanessa cardui - Mari R. Irving; Eric W. Goolsby; Hannah Stanford; Simone Lim-Hing; Maria Urrea; Chase M. Mason (Journal of Chemical Ecology, 2023)
Terpenes are a major class of secondary metabolites present in all plants, and long hypothesized to have diversified in response to specific plant-herbivore interactions. Herbivory is a major biotic interaction that plays out across broad temporal and spatial scales that vary dramatically in temperature regimes, both due to climatic variation across geographic locations as well as the effect of seasonality. In addition, there is an emerging understanding that global climate change will continue to alter the temperature regimes of nearly every habitat on Earth over the coming centuries. Regardless of source, variation in temperature may influence herbivory, in particular via changes in the efficacy and impacts of plant defensive chemistry. This study aims to characterize temperature-driven variation in toxicological effects across several structural classes of terpenes in the model herbivore Vanessa cardui , the painted lady butterfly. We observed a general increase in monoterpene toxicity to larvae, pupa, and adults at higher temperatures, as well as an increase in development time as terpene concentration increased. Results obtained from this study yield insights into possible drivers of seasonal variation in plant terpene production as well as inform effects of rising global temperatures on plant-insect interactions. In the context of other known effects of climate change on plant-herbivore interactions like carbon fertilization and compensatory feeding, temperature-driven changes in plant chemical defense efficacy may further complicate the prediction of climate change impacts on the fundamental ecological process of herbivory.

Globally‐distributed microbial eukaryotes exhibit endemism at deep‐sea hydrothermal vents - Sarah K. Hu; Amy R. Smith; Rika E. Anderson; Sean P. Sylva; Michaela Setzer; Maria Steadmon; Kiana L. Frank; Eric W. Chan; Darlene S. S. Lim; Christopher R. German; John A. Breier; Susan Q. Lang; et al. (Molecular Ecology, 2023)
Single‐celled microbial eukaryotes inhabit deep‐sea hydrothermal vent environments and play critical ecological roles in the vent‐associated microbial food web. 18S rRNA amplicon sequencing of diffuse venting fluids from four geographically‐ and geochemically‐distinct hydrothermal vent fields was applied to investigate community diversity patterns among protistan assemblages. The four vent fields include Axial Seamount at the Juan de Fuca Ridge, Sea Cliff and Apollo at the Gorda Ridge, all in the NE Pacific Ocean, and Piccard and Von Damm at the Mid‐Cayman Rise in the Caribbean Sea. We describe species diversity patterns with respect to hydrothermal vent field and sample type, identify putative vent endemic microbial eukaryotes, and test how vent fluid geochemistry may influence microbial community diversity. At a semi‐global scale, microbial eukaryotic communities at deep‐sea vents were composed of similar proportions of dinoflagellates, ciliates, Rhizaria, and stramenopiles. Individual vent fields supported distinct and highly diverse assemblages of protists that included potentially endemic or novel vent‐associated strains. These findings represent a census of deep‐sea hydrothermal vent protistan communities. Protistan diversity, which is shaped by the hydrothermal vent environment at a local scale, ultimately influences the vent‐associated microbial food web and the broader deep‐sea carbon cycle.

Demography of the understory herb H eliconia acuminata ( H eliconiaceae) in an experimentally fragmented tropical landscape - Emilio M. Bruna; María Uriarte; Maria Rosa Darrigo; Paulo Rubim; Cristiane F. Jurinitz; Eric R. Scott; Osmaildo Ferreira da Silva; W. John Kress (Ecology, 2023)
Habitat fragmentation remains a major focus of research by ecologists decades after being put forward as a threat to the integrity of ecosystems. While studies have documented myriad biotic changes in fragmented landscapes, including the local extinction of species from fragments, the demographic mechanisms underlying these extinctions are rarely known. However, many of them—especially in lowland tropical forests—are thought to be driven by one of two mechanisms: (1) reduced recruitment in fragments resulting from changes in the diversity or abundance of pollinators and seed dispersers or (2) increased rates of individual mortality in fragments due to dramatically altered abiotic conditions, especially near fragment edges. Unfortunately, there have been few tests of these potential mechanisms due to the paucity of long‐term and comprehensive demographic data collected in both forest fragments and continuous forest sites. Here we report 11 years (1998–2009) of demographic data from populations of the Amazonian understory herb Heliconia acuminata (LC Rich.) found at Brazil's Biological Dynamics of Forest Fragments Project (BDFFP). The data set comprises >66,000 plant × year records of 8586 plants, including 3464 seedlings established after the first census. Seven populations were in experimentally isolated fragments (one in each of four 1‐ha fragments and one in each of three 10‐ha fragments), with the remaining six populations in continuous forest. Each population was in a 50 × 100 m permanent plot, with the distance between plots ranging from 500 m to 60 km. The plants in each plot were censused annually, at which time we recorded, identified, marked, and measured new seedlings, identified any previously marked plants that died, and recorded the size of surviving individuals. Each plot was also surveyed four to five times during the flowering season to identify reproductive plants and record the number of inflorescences each produced. These data have been used to investigate topics ranging from the way fragmentation‐related reductions in germination influence population dynamics to statistical methods for analyzing reproductive rates. This breadth of prior use reflects the value of these data to future researchers. In addition to analyses of plant responses to habitat fragmentation, these data can be used to address fundamental questions in plant demography and the evolutionary ecology of tropical plants and to develop and test demographic models and tools. Though we welcome opportunities to collaborate with interested users, there are no restrictions on the use of this data set. However, we do request that those using the data for teaching or research purposes inform us of how they are doing so and cite this paper and the data archive when appropriate. Any publication using the data must also include a BDFFP Technical Series Number in the Acknowledgments. Authors can request this series number upon the acceptance of their article by contacting the BDFFP's Scientific Coordinator or E. M. Bruna.

Chemical profile, in vitro bioactivities, and antinociceptive effect of Red Pitaya extracts on zebrafish - Chayane Gomes Marques; Maurício Fraga van Tilburg; Eric Petterson Viana Pereira; Sandra Machado Lira; Paulo Riceli Vasconcelos Ribeiro; Emanuela de Lima Rebouças; Marcelo Oliveira Holanda; Glauber Batista Moreira Santos; José Ytalo Gomes da Silva; Guilherme Julião Zocolo; Ana Paula Dionísio; Maria Izabel Florindo Guedes; et al. (South African Journal of Botany, 2023)

Capacity gaps in land-based mitigation technologies and practices: A first stock take - Stefan Bößner; Maria Xylia; Bibiana Bilbao; Siti N. Indriani; Moritz Laub; Eric Rahn; Luis D. Virla; Francis X. Johnson (Land Use Policy, 2023)

Dynamic modelling the effects of ionic strength and ion complexation on trace metal speciation during anaerobic digestion - Susan George; Maria Rosaria Mattei; Luigi Frunzo; Giovanni Esposito; Eric D. van Hullebusch; Fernando G. Fermoso (Journal of Environmental Management, 2023)

Mobility of antimony in contrasting surface environments of a mine site: influence of redox conditions and microbial communities - Jesús Daniel Peco; Hugues Thouin; José María Esbrí; Héctor Ricardo Campos-Rodríguez; Eva Maria García-Noguero; Dominique Breeze; Jaime Villena; Eric Gloaguen; Pablo Leon Higueras; Fabienne Battaglia-Brunet (Environmental Science and Pollution Research, 2023)

Social-ecological features of set nets small-scale fisheries in the context of Mediterranean marine protected areas - ANTONIO CALÒ; ANTONIO DI FRANCO; CHARALAMPOS DIMITRIADIS; LEA PIACENTINI; PATRICIA VENTURA; ALEXIS PEY; JOSÉ ANTONIO GARCÍA-CHARTON; ERIC CHARBONNEL; VICTOR DECUGIS; FRANCESCO DE FRANCO; IVONI FOURNARI-KONSTANTINIDOU; JOSIPA GRBIN; et al. (Mediterranean Marine Science, 2023)
The small-scale fisheries (SSF) sector has attracted considerable attention over the last decade due to its major importance in sustaining the livelihoods of coastal communities worldwide, poverty alleviation, food security, social wealth and traditions. Despite this importance, quantitative and qualitative information on SSF is still largely lacking and when available, it tends to be scattered or very localized. SSF are also among the very few professional extractive activities generally allowed within Marine Protected Areas (MPAs), and are therefore expected to acquire further momentum in the near future in light of the projected increase of protected marine surface area due to international commitments. However, SSF associated with areas including MPAs may differ from those operating in unprotected contexts with regard to a range of socio-ecological aspects, thus potentially making management strategies currently in force unsuitable, and requiring the development of ad hoc local and regional policies. Here, we assessed the socio-ecological dimension of SSF operating within and around 11 Mediterranean MPAs, in six EU countries, with the aim of identifying relevant patterns that could inform policy and management relative to this fishing sector in view of the forthcoming increase of the marine surface area under protection. To do so, we have adopted a collaborative approach with fishers and combined a photo-sampling survey of 1,292 set net (mainly trammel-nets) fishing operations at landing with 149 semi-structured interviews with fishers, to gather information on features and catches of SSF fleets (e.g. vessel characteristics, gears, catch composition, catch and revenue per unit of effort). Overall, results highlighted: 1) multiple shared features emerging at regional level (i.e. among the 11 study areas), such as the predominant use of set nets, the major contribution of a limited number of species to the overall catch and revenue, the occurrence in the catch of threatened species and/or undersized individuals; 2) a variety of distinctive socio-ecological features differentiating local SSF communities such as the species mainly contributing to catch and revenue, species size distribution and fleet characteristics. In addition to presenting elements to inform common policies and strategies for SSF management in the context of MPAs, our study provides guidance for the development of a standard methodology for the full documentation of SSF in the Mediterranean Sea.

The synergistic response of primary production in grasslands to combined nitrogen and phosphorus addition is caused by increased nutrient uptake and retention - Eduardo Vázquez; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Rebecca L. McCulley; Anita C. Risch; Eric W. Seabloom; George R. Wheeler; Marie Spohn (Plant and Soil, 2023)
Background and aims A synergistic response of aboveground plant biomass production to combined nitrogen (N) and phosphorus (P) addition has been observed in many ecosystems, but the underlying mechanisms and their relative importance are not well known. We aimed at evaluating several mechanisms that could potentially cause the synergistic growth response, such as changes in plant biomass allocation, increased N and P uptake by plants, and enhanced ecosystem nutrient retention. Methods We studied five grasslands located in Europe and the USA that are subjected to an element addition experiment composed of four treatments: control (no element addition), N addition, P addition, combined NP addition. Results Combined NP addition increased the total plant N stocks by 1.47 times compared to the N treatment, while total plant P stocks were 1.62 times higher in NP than in single P addition. Further, higher N uptake by plants in response to combined NP addition was associated with reduced N losses from the soil (evaluated based on soil δ 15 N) compared to N addition alone, indicating a higher ecosystem N retention. In contrast, the synergistic growth response was not associated with significant changes in plant resource allocation. Conclusions Our results demonstrate that the commonly observed synergistic effect of NP addition on aboveground biomass production in grasslands is caused by enhanced N uptake compared to single N addition, and increased P uptake compared to single P addition, which is associated with a higher N and P retention in the ecosystem.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Development and Evaluation of Brief Web-Based Education for Primary Care Providers to Address Inequities in Lung Cancer Screening and Smoking Cessation Treatment - Laney Smith; Randi M. Williams; Julia Whealan; Allison Windels; Eric D. Anderson; Vicky Parikh; Chavalia Joan Breece; Namita Puran; Andrea K. Shepherd; Maria Geronimo; George Luta; Lucile Adams-Campbell; et al. (Journal of Cancer Education, 2023)

Improved Baited Remote Underwater Video (BRUV) for 24 h Real-Time Monitoring of Pelagic and Demersal Marine Species from the Epipelagic Zone - Alejandro Prat-Varela; Agusti Torres; Daniel Cervantes; Marc Aquino-Baleytó; Ana-Maria Abril; Eric E. G. Clua (Journal of Marine Science and Engineering, 2023)
Bait-based remote underwater video (BRUV) systems are effective devices for remotely observing fish and other marine organisms in challenging environments. The development of a long duration (24 h) surface BRUV observation surveys allowed the monitoring of scarce and elusive pelagic sharks and the direct impact on non-targeted species of longline fishing in the Western Mediterranean. Technological limitations, such as the limited storage capacity and a single surface camera, were improved by (i) adding a deep camera equipped with light (below 80 m depth) and (ii) replacing Gopros with a multi-camera video surveillance system (surface and depth) with a storage capacity of several days and access to real-time observation. Based on a deployment effort of 1884 h video data, we identified 11 blue sharks (Prionace glauca) and one bluntnose sixgill shark (Hexanchus griseus), a deep-sea species that scarcely swims at the surface. The real-time observation capability was a powerful tool for reducing logistical costs and for raising environmental awareness in educational and outreach programmes.

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

Integrating larval connectivity into the marine conservation decision‐making process across spatial scales - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Wahid Suherfian; La Sara; Iliana Chollett; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal connectivity is typically integrated into spatial conservation decisions at regional or national scales, but implementing agencies struggle with translating these methods to local scales. We used larval dispersal connectivity at regional (hundreds of kilometers) and local (tens of kilometers) scales to aid in design of networks of no‐take reserves in Southeast Sulawesi, Indonesia. We used Marxan with Connectivity informed by biophysical larval dispersal models and remotely sensed coral reef habitat data to design marine reserve networks for 4 commercially important reef species across the region. We complemented regional spatial prioritization with decision trees that combined network‐based connectivity metrics and habitat quality to design reserve boundaries locally. Decision trees were used in consensus‐based workshops with stakeholders to qualitatively assess site desirability, and Marxan was used to identify areas for subsequent network expansion. Priority areas for protection and expected benefits differed among species, with little overlap in reserve network solutions. Because reef quality varied considerably across reefs, we suggest reef degradation must inform the interpretation of larval dispersal patterns and the conservation benefits achievable from protecting reefs. Our methods can be readily applied by conservation practitioners, in this region and elsewhere, to integrate connectivity data across multiple spatial scales.

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Agricultural conservation may not help Midwestern US freshwater biodiversity in a changing climate - Qihong Dai; Yong Cao; Maria L. Chu; Eric R. Larson; Cory D. Suski (Science of The Total Environment, 2023)

Distinguishing forest types in restored tropical landscapes with UAV-borne LIDAR - Janneke Scheeres; Johan de Jong; Benjamin Brede; Pedro H.S. Brancalion; Eben Noth Broadbent; Angelica Maria Almeyda Zambrano; Eric Bastos Gorgens; Carlos Alberto Silva; Ruben Valbuena; Paulo Molin; Scott Stark; Ricardo Ribeiro Rodrigues; et al. (Remote Sensing of Environment, 2023)

SCCS Scientific Opinion on Acid Yellow 3 (submission II) – SCCS/1631/21 - Corrado L. Galli (rapporteur); Ulrike Bernauer; Laurent Bodin; Qasim Chaudhry; Pieter Jan Coenraads; Maria Dusinska; Janine Ezendam; Berit Granum; Eric Gaffet; Eirini Panteri; Vera Rogiers; Christophe Rousselle; et al. (Regulatory Toxicology and Pharmacology, 2023)

Relationships between fluid mixing, biodiversity, and chemosynthetic primary productivity in Yellowstone hot springs - Maria C. Fernandes‐Martins; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2023)
The factors that influence biodiversity and productivity of hydrothermal ecosystems are not well understood. Here we investigate the relationship between fluid mixing, biodiversity, and chemosynthetic primary productivity in three co‐localized hot springs (RSW, RSN, and RSE) in Yellowstone National Park that have different geochemistry. All three springs are sourced by reduced hydrothermal fluid, but RSE and RSN receive input of vapour phase gas and oxidized groundwaters, with input of both being substantially higher in RSN. Metagenomic sequencing revealed that communities in RSN were more biodiverse than those of RSE and RSW in all dimensions evaluated. Microcosm activity assays indicate that rates of dissolved inorganic carbon (DIC) uptake were also higher in RSN than in RSE and RSW. Together, these results suggest that increased mixing of reduced volcanic fluid with oxidized fluids generates additional niche space capable of supporting increasingly biodiverse communities that are more productive. These results provide insight into the factors that generate and maintain chemosynthetic biodiversity in hydrothermal systems and that influence the distribution, abundance, and diversity of microbial life in communities supported by chemosynthesis. These factors may also extend to other ecosystems not supported by photosynthesis, including the vast subterranean biosphere and biospheres beneath ice sheets and glaciers.

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

Regulatory safety assessment of nanoparticles for the food chain in Europe - Reinhilde Schoonjans; Jacqueline Castenmiller; Qasim Chaudhry; Francesco Cubadda; Takis Daskaleros; Roland Franz; David Gott; Jan Mast; Alicja Mortensen; Agnes G. Oomen; Hubert Rauscher; Stefan Weigel; et al. (Trends in Food Science & Technology, 2023)

College Students’ Awareness of the Link Between Human Papillomavirus (HPV) and HPV-Associated Cancers - Maria C. Franca; Valerie E. Boyer; Mary A. Gerend; Minjee Lee; Kelli D. Whittington; Stacey L. McKinney; Sandra K. Collins; Richard C. McKinnies; Eric Adjei Boakye (Journal of Cancer Education, 2023)

Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Iliana Chollett; Nils Krueck; Daniel Holstein; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia

SCCS scientific opinion on HAA299 (nano) - SCCS/1634/21 - Corrado Lodovico Galli (rapporteur); Ulrike Bernauer; Laurent Bodin; Qasim Chaudhry; Pieter Jan Coenraads; Maria Dusinska; Janine Ezendam; Eric Gaffet; Berit Granum; Eirini Panteri; Vera Rogiers; Christophe Rousselle; et al. (Regulatory Toxicology and Pharmacology, 2023)

Diverse Effects of Climate, Land Use, and Insects on Dung and Carrion Decomposition - Jana Englmeier; Oliver Mitesser; M. Eric Benbow; Torsten Hothorn; Christian von Hoermann; Caryl Benjamin; Ute Fricke; Cristina Ganuza; Maria Haensel; Sarah Redlich; Rebekka Riebl; Sandra Rojas Botero; et al. (Ecosystems, 2023)
Land-use intensification and climate change threaten ecosystem functions. A fundamental, yet often overlooked, function is decomposition of necromass. The direct and indirect anthropogenic effects on decomposition, however, are poorly understood. We measured decomposition of two contrasting types of necromass, rat carrion and bison dung, on 179 study sites in Central Europe across an elevational climate gradient of 168–1122 m a.s.l. and within both local and regional land uses. Local land-use types included forest, grassland, arable fields, and settlements and were embedded in three regional land-use types (near-natural, agricultural, and urban). The effects of insects on decomposition were quantified by experimental exclusion, while controlling for removal by vertebrates. We used generalized additive mixed models to evaluate dung weight loss and carrion decay rate along elevation and across regional and local land-use types. We observed a unimodal relationship of dung decomposition with elevation, where greatest weight loss occurred between 600 and 700 m, but no effects of local temperature, land use, or insects. In contrast to dung, carrion decomposition was continuously faster with both increasing elevation and local temperature. Carrion reached the final decomposition stage six days earlier when insect access was allowed, and this did not depend on land-use effect. Our experiment identified different major drivers of decomposition on each necromass form. The results show that dung and carrion decomposition are rather robust to local and regional land use, but future climate change and decline of insects could alter decomposition processes and the self-regulation of ecosystems.

SCCS scientific opinion on Butylated hydroxytoluene (BHT) - SCCS/1636/21 - Berit Granum (rapporteur); Ulrike Bernauer; Laurent Bodin; Qasim Chaudhry; Coenraads Pieter Jan; Maria Dusinska; Janine Ezendam; Eric Gaffet; Corrado L. Galli; Eirini Panteri; Vera Rogiers; Christophe Rousselle; et al. (Regulatory Toxicology and Pharmacology, 2023)

Thermoregulation and thermal sensation during whole-body water immersion at different water temperatures in healthy individuals: A scoping review - Maria Ntoumani; Benoit Dugué; Eric Rivas; Konstantina Gongaki (Journal of Thermal Biology, 2023)

Free-living Allen’s hummingbirds (Selasphorus sasin) rarely use torpor while nesting - Erich R. Eberts; Glenn J. Tattersall; Peter J. Auger; Maria Curley; Melissa I. Morado; Eric G. Strauss; Donald R. Powers; Noemi C. Soveral; Bret W. Tobalske; Anusha Shankar (Journal of Thermal Biology, 2023)

The effect modification of extreme temperatures on mental and behavior disorders by environmental factors and individual-level characteristics in Canada - Eric Lavigne; Alana Maltby; Jean-Nicolas Côté; Kate R. Weinberger; Christopher Hebbern; Ana Maria Vicedo-Cabrera; Piotr Wilk (Environmental Research, 2023)

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Review of Environmental Monitoring by Means of Radio Waves in the Polar Regions: From Atmosphere to Geospace - Lucilla Alfonsi; Nicolas Bergeot; Pierre J. Cilliers; Giorgiana De Franceschi; Lisa Baddeley; Emilia Correia; Domenico Di Mauro; Carl-Fredrik Enell; Mark Engebretson; Reza Ghoddousi-Fard; Ingemar Häggström; Young-bae Ham; et al. (Surveys in Geophysics, 2022)
The Antarctic and Arctic regions are Earth's open windows to outer space. They provide unique opportunities for investigating the troposphere–thermosphere–ionosphere–plasmasphere system at high latitudes, which is not as well understood as the mid- and low-latitude regions mainly due to the paucity of experimental observations. In addition, different neutral and ionised atmospheric layers at high latitudes are much more variable compared to lower latitudes, and their variability is due to mechanisms not yet fully understood. Fortunately, in this new millennium the observing infrastructure in Antarctica and the Arctic has been growing, thus providing scientists with new opportunities to advance our knowledge on the polar atmosphere and geospace. This review shows that it is of paramount importance to perform integrated, multi-disciplinary research, making use of long-term multi-instrument observations combined with ad hoc measurement campaigns to improve our capability of investigating atmospheric dynamics in the polar regions from the troposphere up to the plasmasphere, as well as the coupling between atmospheric layers. Starting from the state of the art of understanding the polar atmosphere, our survey outlines the roadmap for enhancing scientific investigation of its physical mechanisms and dynamics through the full exploitation of the available infrastructures for radio-based environmental monitoring.

Genotyping-by-sequencing of passion fruit (Passiflora spp.) generates genomic resources for breeding and systematics - Joshua D. Anderson; Ravena Ferreira Vidal; Maria Brym; Eric T. Stafne; Marcio F. R. Resende; Alexandre Pio Viana; Alan H. Chambers (Genetic Resources and Crop Evolution, 2022)

Atrial fibrosis identification with unipolar electrogram eigenvalue distribution analysis in multi-electrode arrays - Jennifer Riccio; Alejandro Alcaine; Sara Rocher; Laura Martinez-Mateu; Javier Saiz; Eric Invers-Rubio; Maria S. Guillem; Juan Pablo Martínez; Pablo Laguna (Medical & Biological Engineering & Computing, 2022)
Atrial fibrosis plays a key role in the initiation and progression of atrial fibrillation (AF). Atrial fibrosis is typically identified by a peak-to-peak amplitude of bipolar electrograms (b-EGMs) lower than 0.5 mV, which may be considered as ablation targets. Nevertheless, this approach disregards signal spatiotemporal information and b-EGM sensitivity to catheter orientation. To overcome these limitations, we propose the dominant-to-remaining eigenvalue dominance ratio (EIGDR) of unipolar electrograms (u-EGMs) within neighbor electrode cliques as a waveform dispersion measure, hypothesizing that it is correlated with the presence of fibrosis. A simulated 2D tissue with a fibrosis patch was used for validation. We computed EIGDR maps from both original and time-aligned u-EGMs, denoted as $$\mathcal {R}$$ R and $$\mathcal{R}^{\mathcal{A}}$$ R A , respectively, also mapping the gain in eigenvalue concentration obtained by the alignment, $$Δ \mathcal{R}^{\mathcal{A}}$$ Δ R A . The performance of each map in detecting fibrosis was evaluated in scenarios including noise and variable electrode-tissue distance. Best results were achieved by $$\mathcal{R}^{\mathcal{A}}$$ R A , reaching 94% detection accuracy, versus the 86% of b-EGMs voltage maps. The proposed strategy was also tested in real u-EGMs from fibrotic and non-fibrotic areas over 3D electroanatomical maps, supporting the ability of the EIGDRs as fibrosis markers, encouraging further studies to confirm their translation to clinical settings. Graphical Abstract Upper panels: map of $$\mathcal {R}^{\mathcal {A}}$$ R A from 3×3 cliques for Ψ= 0 ∘ and bipolar voltage map V b - m , performed assuming a variable electrode-to-tissue distance and noisy u-EGMs (noise level σ v = 46.4 μ V ). Lower panels: detected fibrotic areas (brown), using the thresholds that maximize detection accuracy of each map

Two constructed wetlands within a Mediterranean natural park immersed in an agrolandscape reduce most heavy metal water concentrations and dampen the majority of pesticide presence - Maria A. Rodrigo; Eric Puche; Nuria Carabal; Sergio Armenta; Francesc A. Esteve-Turrillas; Javier Jiménez; Fernando Juan (Environmental Science and Pollution Research, 2022)
The water concentrations of 12 heavy and other metals/metalloids were analyzed seasonally along two horizontal-flow constructed wetlands (CWs) (Tancat Mília—TM and Tancat l’Illa—TLI) located within the Mediterranean Albufera de València Natural Park during 2020–2021. A wide-scope screening of pesticides present in waters was also performed. The two CWs were created to improve water quality and increase biodiversity. They currently receive effluent waters from two different tertiary-treatment wastewater plants, and the water flows along the CWs before being discharged into the main lagoon and a smaller lagoon in TM and TLI, respectively. TLI manages to reduce (Mn) or maintain the concentration of most of the studied elements (Zn, Ni, Hg, Cr, Fe Cd, Cu) at the same level as outside (67%). Only Al, Pb, B, and As remain at a higher concentration. TM also reduces Zn and Cu and keeps the concentration of Cr, Cd, and Hg (representing 42%). Al, Pb, B, and As remain at higher concentrations, as in TLI, but Ni, Fe, and Mn are also at higher concentrations. Although both CWs vary in their ability to remove elements, no risks to human health or the environment have been detected due to the low metal concentration in their outlets, all of them (except Hg) below the legal limits for environmental quality in the European Union. With the detection of 71 compounds in water in each CW area (26 herbicides, 26 insecticides, and 19 fungicides in TLI, and 29 herbicides, 23 insecticides, and 19 fungicides in TM), we also provide evidence of the impact of pesticides, which depends on the application method (helicopter, tractor), originated from areas with high agricultural pressure (chiefly rice crops) on systems (mainly TM) created to preserve biodiversity. Nevertheless, both systems provide crucial environmental services in water quality in this agrolandscape.

Nitrogen but not phosphorus addition affects symbiotic N2 fixation by legumes in natural and semi-natural grasslands located on four continents - Eduardo Vázquez; Per-Marten Schleuss; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Nico Eisenhauer; Anu Eskelinen; Philip A. Fay; Sylvia Haider; Anke Jentsch; Kevin P. Kirkman; Rebecca L. McCulley; et al. (Plant and Soil, 2022)
Background and aims The amount of nitrogen (N) derived from symbiotic N 2 fixation by legumes in grasslands might be affected by anthropogenic N and phosphorus (P) inputs, but the underlying mechanisms are not known. Methods We evaluated symbiotic N 2 fixation in 17 natural and semi-natural grasslands on four continents that are subjected to the same full-factorial N and P addition experiment, using the 15 N natural abundance method. Results N as well as combined N and P (NP) addition reduced aboveground legume biomass by 65% and 45%, respectively, compared to the control, whereas P addition had no significant impact. Addition of N and/or P had no significant effect on the symbiotic N 2 fixation per unit legume biomass. In consequence, the amount of N fixed annually per grassland area was less than half in the N addition treatments compared to control and P addition, irrespective of whether the dominant legumes were annuals or perennials. Conclusion Our results reveal that N addition mainly impacts symbiotic N 2 fixation via reduced biomass of legumes rather than changes in N 2 fixation per unit legume biomass. The results show that soil N enrichment by anthropogenic activities significantly reduces N 2 fixation in grasslands, and these effects cannot be reversed by additional P amendment.

Versatile aquarium for jellyfish: A rearing system for the biomass production of early life stages in flow-through or closed systems - Ainara Ballesteros; Pedro Siles; Eric Jourdan; Josep-Maria Gili (Frontiers in Marine Science, 2022)
Interest in the rearing of jellyfish has grown exponentially over recent years due to their indisputable potential in a wide variety of uses and research. Here, we describe the design and operation of an effective modified kreisel aquarium that allows to grow of the early planktonic life stages of jellyfish in both flow-through or closed systems. Thanks to its versatile and innovative approach, the aquarium operates for species with a metagenetic life cycle, and allows the metamorphosis of ephyrae from fertilized eggs for species with a holoplanktonic life cycle, such as Pelagia noctiluca . In addition, its configuration allows the mesh screen to be changed in situ , adjusting the size of the mesh according to the growth of the jellyfish and the size of the prey offered. An accessory, named the polyp plate, suspends the polyps in a downward or sideways position, facilitating prey capture, strobilae formation and release of ephyrae. The improvements of this modified kreisel reduce the time-involvement for staff in maintenance routines, and it is an important contribution to jellyfish husbandry techniques and biomass production. These improvements especially target to the culture of the blooming and stinging P. noctiluca , which has been noted to present a host of challenges to the scientific and aquarist communities.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Innovative technologies to remove alkylphenols from wastewater: a review - Grégorio Crini; Cesare Cosentino; Corina Bradu; Marc Fourmentin; Giangiacomo Torri; Olim Ruzimuradov; Idil Arslan Alaton; Maria Concetta Tomei; Ján Derco; Mondher Barhoumi; Helena Prosen; Borislav N. Malinović; et al. (Environmental Chemistry Letters, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Ranking the sustainable development goals: perceived sustainability priorities in small island states - Maarten B. Eppinga; Eric N. Mijts; Maria J. Santos (Sustainability Science, 2022)
The Sustainable Development Goals (SDGs) aim to elicit global mobilization to implement the 2030 Agenda for Sustainable Development, and are increasingly used in support of Education for Sustainable Development (ESD). Previous studies have highlighted interdependencies between SDGs, with potential interactions between four Sustainability Domains: Economy, Governance, Planet and Society. This study aimed to assess whether people’s perception of the relative importance of the SDGs reflects recognition of the need to prioritize efforts across Domains, or whether this perception is based on different valuations of the Sustainability Domains themselves. We designed an interactive online tool in which participants used the Q-sort technique to rank the SDGs according to their subjective valuation of importance. We analyzed the rankings of 108 participants, all learners at universities in three Small Island States (SIS): Aruba, Suriname and Trinidad and Tobago. Analysis of the correlation structure among participants’ Q-sorts showed that higher perceived importance of the Society- and Economy-related SDGs 2, 3, 4, 8 and 9 traded off with lower perceived importance of the Planet-related SDGs 13, 14 and 15. Furthermore, SDG rankings of learners from Aruba occurred furthest toward the Planet-based part of this trade-off axis. For ESD programs, our method provides a novel tool to identify key interactions between SDGs that may not yet be recognized by program participants. In this way, communicating the need for simultaneous action and policy development across Sustainability Domains could be specifically tailored to the local context. Such connections may increase the effectiveness of ESD in addressing the substantial sustainability challenges facing SIS.

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

A New Long-Term Photovoltaic Power Forecasting Model Based on Stacking Generalization Methodology - Eric Ofori-Ntow Jnr; Yao Yevenyo Ziggah; Maria Joao Rodrigues; Susana Relvas (Natural Resources Research, 2022)

Drone-based photogrammetry assessments of body size and body condition of Antillean manatees - Eric Angel Ramos; Sarah Landeo-Yauri; Nataly Castelblanco-Martínez; Maria Renée Arreola; Adam H. Quade; Guillaume Rieucau (Mammalian Biology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Successful Culture of Pelagia noctiluca (Cnidaria: Scyphozoa) Over Time: A Continuous Supply of the Holoplanktonic Jellyfish for Research and Industrial Applications - Ainara Ballesteros; Diego Páez; Andreu Santín; Alba García; Yeray Martín; Ester Alonso; Eric Jourdan; Josep-Maria Gili (Frontiers in Marine Science, 2022)
The scyphozoan Pelagia noctiluca has potential value for research and a wide variety of industrial applications. However, its holoplanktonic life cycle makes it difficult to maintain a permanent stock in aquaculture, unlike the continuous supply of newly-released ephyrae from jellyfish species with a benthic life stage. We investigated optimal feeding conditions for the captive breeding of P. noctiluca , monitoring total body diameter, morphological development, survival rate, and instantaneous growth rate. Diets of different items encapsulated in gelatin or non-motile prey were not suitable for successful growth of the early stages (ephyra and metaephyra), whereas rotifers were a sufficient food source for healthy growth. Fertilized eggs from sexually-mature jellyfish were obtained at 84.5 ± 2.1 and 87.0 ± 9.9 days post-fecundation in the presence and absence of gelatinous prey ( Aurelia sp.), respectively. In contrast with the general consensus, we demonstrate that the incorporation of medusivorous prey was not essential for proper growth and closure of P. noctiluca life cycle. Instead, we recommend the inclusion of white shrimps ( Acetes sp.) for the formation and maturation of gonads and production of eggs. Instantaneous growth rates (57.0% d -1 ), the highest reported to date for this species in captive conditions, were higher during the early stages. A third generation of cultured P. noctiluca was obtained for the first time (169 – 179 experimental days), demonstrating the durability of the culture, providing permanent stock and halving the production time of mature individuals compared to previous studies. Finally, we validated the use of captive-bred specimens through quantification of the hemolytic area after the sting process using the tentacle skin blood agarose assay methodology.

Current Advances and Challenges in Fisheries and Aquaculture Science - Eric Hallerman; Maria Angeles Esteban; Bernardo Baldisserotto (Fishes, 2022)
Advances in fisheries and aquaculture science often follow the introduction of new tools or analytic methods [...]

Towards progressive regulatory approaches for agricultural applications of animal biotechnology - Eric M. Hallerman; Justin P. Bredlau; Luiz Sergio A. Camargo; Maria Lucia Zaidan Dagli; Margaret Karembu; Godfrey Ngure; Rhodora Romero-Aldemita; Pedro Jesús Rocha-Salavarrieta; Mark Tizard; Mark Walton; Diane Wray-Cahen (Transgenic Research, 2022)
Traditional breeding techniques, applied incrementally over thousands of years, have yielded huge benefits in the characteristics of agricultural animals. This is a result of significant, measurable changes to the genomes of those animal species and breeds. Genome editing techniques may now be applied to achieve targeted DNA sequence alterations, with the potential to affect traits of interest to production of agricultural animals in just one generation. New opportunities arise to improve characteristics difficult to achieve or not amenable to traditional breeding, including disease resistance, and traits that can improve animal welfare, reduce environmental impact, or mitigate impacts of climate change. Countries and supranational institutions are in the process of defining regulatory approaches for genome edited animals and can benefit from sharing approaches and experiences to institute progressive policies in which regulatory oversight is scaled to the particular level of risk involved. To facilitate information sharing and discussion on animal biotechnology, an international community of researchers, developers, breeders, regulators, and communicators recently held a series of seven virtual workshop sessions on applications of biotechnology for animal agriculture, food and environmental safety assessment, regulatory approaches, and market and consumer acceptance. In this report, we summarize the topics presented in the workshop sessions, as well as discussions coming out of the breakout sessions. This is framed within the context of past and recent scientific and regulatory developments. This is a pivotal moment for determination of regulatory approaches and establishment of trust across the innovation through-chain, from researchers, developers, regulators, breeders, farmers through to consumers.

Nutrients and herbivores impact grassland stability across spatial scales through different pathways - Qingqing Chen; Shaopeng Wang; Eric W. Seabloom; Andrew S. MacDougall; Elizabeth T. Borer; Jonathan D. Bakker; Ian Donohue; Johannes M. H. Knops; John W. Morgan; Oliver Carroll; Mick Crawley; Miguel N. Bugalho; et al. (Global Change Biology, 2022)
Nutrients and herbivores are well‐known drivers of grassland diversity and stability in local communities. However, whether they interact to impact the stability of aboveground biomass and whether these effects depend on spatial scales remain unknown. It is also unclear whether nutrients and herbivores impact stability via different facets of plant diversity including species richness, evenness, and changes in community composition through time and space. We used a replicated experiment adding nutrients and excluding herbivores for 5 years in 34 global grasslands to explore these questions. We found that both nutrient addition and herbivore exclusion alone reduced stability at the larger spatial scale (aggregated local communities; gamma stability), but through different pathways. Nutrient addition reduced gamma stability primarily by increasing changes in local community composition over time, which was mainly driven by species replacement. Herbivore exclusion reduced gamma stability primarily by decreasing asynchronous dynamics among local communities (spatial asynchrony). Their interaction weakly increased gamma stability by increasing spatial asynchrony. Our findings indicate that disentangling the processes operating at different spatial scales may improve conservation and management aiming at maintaining the ability of ecosystems to reliably provide functions and services for humanity.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Toxicity indicators and biochemical responses in leaves of ‘Tahiti’ acid lime grafted on ten Citrus rootstocks under salt stress - Maria da Saúde de Sousa Ribeiro; Marcos Eric Barbosa Brito; Claudivan Feitosa Lacerda; Luderlândio de Andrade Silva; Walter dos Santos Soares Filho; Antonia Leila Rocha Neves; Isabel Cristina da Silva Araújo; Cibelle Gomes Gadelha (Theoretical and Experimental Plant Physiology, 2022)

Ocean Acidification Affects Volatile Infochemicals Production and Perception in Fauna and Flora Associated With Posidonia oceanica (L.) Delile - Mirko Mutalipassi; Valerio Mazzella; Matthias Schott; Patrick Fink; Francesca Glaviano; Lucia Porzio; Maurizio Lorenti; Maria Cristina Buia; Eric von Elert; Valerio Zupo (Frontiers in Marine Science, 2022)
Communication among marine organisms are generally based on production, transmission, and interpretation of chemical cues. Volatile organic compounds (VOCs) can act as infochemicals, and ocean acidification can alter their production in the source organisms as well as the interpretation of the information they drive to target organisms. Two diatoms ( Cocconeis scutellum var. parva and Diploneis sp.) and a macroalga ( Ulva prolifera ), all common epiphytes of Posidonia oceanica leaves, were isolated and cultured at two pH conditions (8.2 and 7.7). Their biomass was collected, and the VOCs produced upon wounding were extracted and analyzed using gas chromatography. Chemotactic reactions of invertebrates triggered by VOCs were tested using a static choice experimental arena and a flow-through flume system. Odor choice experiments were performed on several invertebrates associated with P. oceanica meadows to investigate the modification of behavioral responses due to the growth of algae in acidified environments. Complex patterns of behavioral responses were recorded after exposure to algal VOCs. This study demonstrated that a) ocean acidification alters the bouquet of VOCs released by diatoms and macroalgae and b) these compounds act as infochemicals and trigger peculiar behavioral responses in benthic invertebrates. In addition, behavioral responses are species-specific, dose-dependent, and are modified by environmental constraints. In fact, the static diffusion in choice arenas produced different responses as compared to flow-through flume systems. In conclusion, we demonstrate that in future marine environments higher CO 2 concentrations (leading to a pH 7.7 by the end of this century) will modify the production of VOCs by micro- and macroalgae as well as the recognition of these infochemicals by marine invertebrates.

The farming and husbandry of Colossoma macropomum : From Amazonian waters to sustainable production - Alexandre Wagner Silva Hilsdorf; Eric Hallerman; Gustavo Moraes Ramos Valladão; Micheli Zaminhan‐Hassemer; Diogo Teruo Hashimoto; Jony Koji Dairiki; Leonardo Susumu Takahashi; Francielly Corrêa Albergaria; Maria Emília de Sousa Gomes; Rossana Luiza Leite Venturieri; Renata Guimarães Moreira; José Eurico Possebon Cyrino (Reviews in Aquaculture, 2022)
Within the rich diversity of South American freshwater fish, Colossoma macropomum (Characiformes: Serrasalmidae), known as tambaqui, cachama or blackfin pacu, can reach 30 kg, is a traditional product in regional fish markets and has drawn the attention of fish farmers since the 1930s. Considerable progress achieved in different fields of aquaculture science has contributed to the growth of tambaqui production. Tambaqui has proven suitable for both monoculture and polyculture systems, and for both extensive and intensive production systems aimed at achieving sustainable, higher productivity with minimal environmental impact. Studies of the reproductive anatomy and physiology of the species proved fundamental to development of techniques to boost commercial production, contributing to development of protocols for hormonally induced spawning and artificial propagation in the 1970s. Newly hatched larvae must be fed with live foods until they can be weaned to artificial feeds at about 100 mg weight. Despite its importance for aquaculture, only a few studies have reported components of quantitative genetic variance and parameters for weight at age, morphometric traits and disease resistance. Genomic tools currently available can be applied to detect variation relevant to performance and to accelerate the process of genetic improvement. While the species’ feeding habit allows the use of diets containing 75%–85% plant protein, much more work needs to be done to optimize aquafeeds. Refinement of tambaqui production methods has the potential to significantly boost South American aquaculture. We recommend research on diets, genetic improvement and system optimization to spur further productivity and achieve sustainable tambaqui culture.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Soil properties as key predictors of global grassland production: Have we overlooked micronutrients? - Dajana Radujković; Erik Verbruggen; Eric W. Seabloom; Michael Bahn; Lori A. Biederman; Elizabeth T. Borer; Elizabeth H. Boughton; Jane A. Catford; Matteo Campioli; Ian Donohue; Anne Ebeling; Anu Eskelinen; et al. (Ecology Letters, 2021)
Fertilisation experiments have demonstrated that nutrient availability is a key determinant of biomass production and carbon sequestration in grasslands. However, the influence of nutrients in explaining spatial variation in grassland biomass production has rarely been assessed. Using a global dataset comprising 72 sites on six continents, we investigated which of 16 soil factors that shape nutrient availability associate most strongly with variation in grassland aboveground biomass. Climate and N deposition were also considered. Based on theory‐driven structural equation modelling, we found that soil micronutrients (particularly Zn and Fe) were important predictors of biomass and, together with soil physicochemical properties and C:N, they explained more unique variation (32%) than climate and N deposition (24%). However, the association between micronutrients and biomass was absent in grasslands limited by NP. These results highlight soil properties as key predictors of global grassland biomass production and point to serial co‐limitation by NP and micronutrients.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Limited thermal acclimation of photosynthesis in tropical montane tree species - Mirindi Eric Dusenge; Maria Wittemann; Myriam Mujawamariya; Elisée B. Ntawuhiganayo; Etienne Zibera; Bonaventure Ntirugulirwa; Danielle A. Way; Donat Nsabimana; Johan Uddling; Göran Wallin (Global Change Biology, 2021)
The temperature sensitivity of physiological processes and growth of tropical trees remains a key uncertainty in predicting how tropical forests will adjust to future climates. In particular, our knowledge regarding warming responses of photosynthesis, and its underlying biochemical mechanisms, is very limited. We grew seedlings of two tropical montane rainforest tree species, the early‐successional species Harungana montana and the late‐successional species Syzygium guineense , at three different sites along an elevation gradient, differing by 6.8℃ in daytime ambient air temperature. Their physiological and growth performance was investigated at each site. The optimum temperature of net photosynthesis ( T optA ) did not significantly increase in warm‐grown trees in either species. Similarly, the thermal optima ( T optV and T optJ ) and activation energies ( E aV and E aJ ) of maximum Rubisco carboxylation capacity ( V cmax ) and maximum electron transport rate ( J max ) were largely unaffected by warming. However, V cmax , J max and foliar dark respiration ( R d ) at 25℃ were significantly reduced by warming in both species, and this decline was partly associated with concomitant reduction in total leaf nitrogen content. The ratio of J max / V cmax decreased with increasing leaf temperature for both species, but the ratio at 25℃ was constant across sites. Furthermore, in H . montana , stomatal conductance at 25℃ remained constant across the different temperature treatments, while in S . guineense it increased with warming. Total dry biomass increased with warming in H . montana but remained constant in S . guineense . The biomass allocated to roots, stem and leaves was not affected by warming in H . montana , whereas the biomass allocated to roots significantly increased in S . guineense . Overall, our findings show that in these two tropical montane rainforest tree species, the capacity to acclimate the thermal optimum of photosynthesis is limited while warming‐induced reductions in respiration and photosynthetic capacity rates are tightly coupled and linked to responses of leaf nitrogen.

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Numerical and Physical Modelling of Wave Overtopping on a Smooth Impermeable Dike with Promenade under Strong Incident Waves - Maria Graça Neves; Eric Didier; Moisés Brito; María Clavero (Journal of Marine Science and Engineering, 2021)
This paper presents a study of run-up/overtopping over a smooth impermeable dike with promenade using 2D and 3D mesh-based and mesh-free numerical models and results from 2D physical modelling for strong energetic incident waves. These waves induce plunging wave breaking and a complex water/air mixture turbulent flow before overtopped the dike, a challenging configuration for numerical models. The analysis is structured in two phases: (i) evaluates the results of 2D numerical and physical models for run-up and overtopping; (ii) compares qualitatively the results of 3D numerical models for overtopping over a dike with promenade between groins located in front of a slope beach. The results indicate that the main differences obtained in run-up and overtopping are due to differences in wave generation and active absorption systems used in physical and numerical models and in turbulent models used by the numerical models. These differences lead to changes on incident wave height and on wave breaking and, consequently, on reflection, run-up and overtopping over the structure. For 3D simulation, even if larger discrepancies were found on overtopping along the dike, mean wave overtopping discharge and water flow height at the crest of the groin head show a similar order of magnitude.

Fishes Receives Its First Impact Factor - Maria Angeles Esteban; Bernardo Baldisserotto; Eric Hallerman (Fishes, 2021)
“A new journey for Fishes” [...]

Incidence, clinical characteristics, risk factors and outcomes of meningoencephalitis in patients with COVID-19 - Marcos Fragiel; Òscar Miró; Pere Llorens; Sònia Jiménez; Pascual Piñera Salmerón; Guillermo Burillo-Putze; Alfonso Martín; Francisco Javier Martín-Sánchez; Eric Jorge García Lamberechts; Javier Jacob; Aitor Alquézar-Arbé; Ferran Llopis-Roca; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effects of clonidine on progressive ratio schedule performance in Fmr1 knockout mice - Craige C. Wrenn; Eric French; Dustin Baker; Randall McCallian; Ryan Kirk; Mark P. Reilly; Maria G. Valdovinos (Psychopharmacology, 2021)

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

Norovirus strains in patients with acute gastroenteritis in rural and low-income urban areas in northern Brazil - Rory J. Tinker; Antonio Charlys da Costa; Roozbeh Tahmasebi; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Ramendra Pati Pandey; Alexis José-Abrego; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Mariana Sequetin Cunha; Emerson Luiz Lima Araújo; Mariela Martínez Gómez; et al. (Archives of Virology, 2021)

Artisanal mining impacts small mammals while chainsaw milling is a more sustainable practice in Ghana - Eric Adjei Lawer; Anne-Christine Mupepele; Alexandra-Maria Klein (Biodiversity and Conservation, 2021)
Logging and mining are widespread in most West African countries and considering their socio-economic importance, little is known about their ecological impacts. In this study, we investigated the effects of chainsaw milling (logging) and artisanal mining on terrestrial small mammal communities in a tropical forest in Ghana. For this, we compared abundance, diversity measures and community composition of small mammals active at the forest floor in logged, mined and undisturbed forest sites. We found that abundance was higher in logged and undisturbed forest sites than in mined sites. Small mammal species richness, Shannon diversity and Pielou’s evenness did not differ significantly among the three forest disturbance categories. Community composition of small mammals varied between mined and undisturbed sites as well as between mined and logged sites, suggesting differential species responses to altered environments. This may be due to the presence of pits in mined forest sites, hence a reduction in exploitable ground habitat structures for shelter, nesting or food. Overall, our results suggest that artisanal mining has strong impacts on community composition of forest floor small mammals in tropical forests while the effect of logging by chainsaw milling activities is minimal, especially when practiced at low intensity. This effect was moderated by elevation and distance to streams that equally shaped small mammal communities. More research on the effects of specific forms of logging and mining activities on small mammals are urgently needed to better protect species in forests impacted by logging and mining.

Trends in flow intermittence for European rivers - Yves Tramblay; Agnieszka Rutkowska; Eric Sauquet; Catherine Sefton; Gregor Laaha; Marzena Osuch; Teresa Albuquerque; Maria Helena Alves; Kazimierz Banasik; Aurelien Beaufort; Luca Brocca; Stefania Camici; et al. (Hydrological Sciences Journal, 2021)

Additive effect of the root-lesion nematode Pratylenchus penetrans and the fungus Rhizoctonia solani on potato yield and damage - Maria Viketoft; Adam Flöhr; Jan-Eric Englund; Jonas Kardell; Eva Edin (Journal of Plant Diseases and Protection, 2020)
The significance of nematodes for disease development caused by other soil-borne pathogens has been demonstrated in many crops throughout the world and specifically prevalent are interactions between plant-parasitic nematodes and species of plant pathogenic fungi. Here, the interaction between the fungus Rhizoctonia solani (AG2) and the migratory endoparasitic root-lesion nematode Pratylenchus penetrans was investigated on potato. The hypotheses were that the combination of R. solani and P. penetrans would result in more severe canker lesions, reduced quality of the tubers and lower tuber yield, and we also expected higher nematode levels to render more nematode damage. To test this, potato plants were grown in pots in two replicate experiments and the presence and/or abundance of the two pathogens were controlled. The first three hypotheses were rejected as (1) the tuber yield decreased when the fungus and nematode occurred together but not more than the sum of their separate effects, i.e. additive, (2) there was no effect of presence of nematodes on the incidence of stem canker, and (3) the quality of tubers was actually partly improved as the presence of the nematodes reduced the likelihood of elephant hide on the tubers in one of the experiments. As expected, there were more visible nematode damages with addition of more nematodes, but beyond that the different nematode levels rendered in most cases similar responses. To have knowledge about interactions between pathogens, as the one showed here, is essential for disease control through appropriate management methods.

Roundup® disrupts chitinolytic enzyme activity and ecdysteroid concentration in Macrobrachium potiuna - Madson Silveira de Melo; Evelise Maria Nazari; Yara Maria Rauh Müller; Eric Gismondi (Environmental Science and Pollution Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Intercomparison of Large-Eddy Simulations of the Antarctic Boundary Layer for Very Stable Stratification - Fleur Couvreux; Eric Bazile; Quentin Rodier; Björn Maronga; Georgios Matheou; Maria J. Chinita; John Edwards; Bart J. H. van Stratum; Chiel C. van Heerwaarden; Jing Huang; Arnold F. Moene; Anning Cheng; et al. (Boundary-Layer Meteorology, 2020)

Geometry of the ideal free distribution: individual behavioural variation and annual reproductive success in aggregations of a social ungulate - Maegwin Bonar; Keith P. Lewis; Quinn M. R. Webber; Maria Dobbin; Michel P. Laforge; Eric Vander Wal (Ecology Letters, 2020)
Variation in social environment can mitigate risks and rewards associated with occupying a particular patch. We aim to integrate Ideal Free Distribution (IFD) and Geometry of the Selfish Herd (GSH) to address an apparent conflict in their predictions of equal mean fitness between patches (IFD) and declining fitness benefits within a patch (GSH). We tested these hypotheses in a socio‐spatial context using individual caribou that were aggregated or disaggregated during calving and varied in their annual reproductive success (ARS). We then tested individual consistency of these spatial tactics. We reveal that two socio‐spatial tactics accorded similar mean ARS (IFD); however, ARS for aggregated individuals declined near the periphery (GSH). Individuals near the aggregation periphery exhibited flexibility, whereas others were consistent. The integration of classical theories through a contemporary lens of consistent individual differences provides evidence for an integrated GSH and IFD strategy that may represent an evolutionary stable state.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

A First Global Oceanic Compilation of Observational Dissolved Aluminum Data With Regional Statistical Data Treatment - Jan-Lukas Menzel Barraqueta; Saumik Samanta; Eric P. Achterberg; Andrew R. Bowie; Peter Croot; Ryan Cloete; Tara De Jongh; Maria D. Gelado-Caballero; Jessica K. Klar; Rob Middag; Jean C. Loock; Tomas A. Remenyi; et al. (Frontiers in Marine Science, 2020)

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

A Time-Extended (24 h) Baited Remote Underwater Video (BRUV) for Monitoring Pelagic and Nocturnal Marine Species - Agusti Torres; Ana-Maria Abril; Eric E. G. Clua (Journal of Marine Science and Engineering, 2020)
Baited remote underwater video systems (BRUVs) are efficient devices for remotely characterising the assemblage and relative density of fishes and other marine organisms. However, technological constraints (e.g., battery life and limited storage memory) typically limit deployment times to

Lumbar spinal cord microglia exhibited increased activation in aging dogs compared with young adult dogs - Christine M. Toedebusch; Virginia B. Garcia; John C. Snyder; Maria R. Jones; David J Schulz; Gayle C. Johnson; Eric Villalón; Joan R. Coates; Michael L. Garcia (GeroScience, 2020)

Into the bloom: Molecular response of pelagic tunicates to fluctuating food availability - Paolo Sordino; Salvatore D'Aniello; Eric Pelletier; Patrick Wincker; Valeria Nittoli; Lars Stemmann; Maria Grazia Mazzocchi; Fabien Lombard; Daniele Iudicone; Luigi Caputi (Molecular Ecology, 2020)
The planktonic tunicates appendicularians and thaliaceans are highly efficient filter feeders on a wide range of prey size including bacteria and have shorter generation times than any other marine grazers. These traits allow some tunicate species to reach high population densities and ensure their success in a favourable environment. However, there are still few studies focusing on which genes and gene pathways are associated with responses of pelagic tunicates to environmental variability. Herein, we present the effect of food availability increase on tunicate community and gene expression at the Marquesas Islands (South‐East Pacific Ocean). By using data from the Tara Oceans expedition, we show that changes in phytoplankton density and composition trigger the success of a dominant larvacean species (an undescribed appendicularian). Transcriptional signature to the autotroph bloom suggests key functions in specific physiological processes, i.e., energy metabolism, muscle contraction, membrane trafficking, and proteostasis. The relative abundance of reverse transcription‐related Pfams was lower at bloom conditions, suggesting a link with adaptive genetic diversity in tunicates in natural ecosystems. Downstream of the bloom, pelagic tunicates were outcompeted by copepods. Our work represents the first metaomics study of the biological effects of phytoplankton bloom on a key zooplankton taxon.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

Upscaling of the single-phase flow and heat transport in fractured geothermal reservoirs using nonlocal multicontinuum method - Maria Vasilyeva; Masoud Babaei; Eric T. Chung; Valentin Alekseev (Computational Geosciences, 2019)

Metal Resistance in Bacteria from Contaminated Arctic Sediment is Driven by Metal Local Inputs - Simona Caputo; Maria Papale; Carmen Rizzo; Stefania Giannarelli; Antonella Conte; Federica Moscheo; Marco Graziano; Paul Eric Aspholm; Massimo Onor; Emilio De Domenico; Stefano Miserocchi; Luigi Michaud; et al. (Archives of Environmental Contamination and Toxicology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

Effects of low glyphosate-based herbicide concentrations on endocrine-related gene expression in the decapoda Macrobrachium potiuna - Madson Silveira de Melo; Evelise Maria Nazari; Célia Joaquim-Justo; Yara Maria Rauh Muller; Eric Gismondi (Environmental Science and Pollution Research, 2019)

The molecular biogeography of the Indo‐Pacific: Testing hypotheses with multispecies genetic patterns - Eric D. Crandall; Cynthia Riginos; Chris E. Bird; Libby Liggins; Eric Treml; Maria Beger; Paul H. Barber; Sean R. Connolly; Peter F. Cowman; Joseph D. DiBattista; Jeff A. Eble; Sharon F. Magnuson; et al. (Global Ecology and Biogeography, 2019)
Aim To test hypothesized biogeographic partitions of the tropical Indo‐Pacific Ocean with phylogeographic data from 56 taxa, and to evaluate the strength and nature of barriers emerging from this test. Location The Indo‐Pacific Ocean. Time period Pliocene through the Holocene. Major taxa studied Fifty‐six marine species. Methods We tested eight biogeographic hypotheses for partitioning of the Indo‐Pacific using a novel modification to analysis of molecular variance. Putative barriers to gene flow emerging from this analysis were evaluated for pairwise Φ ST , and these Φ ST distributions were compared to distributions from randomized datasets and simple coalescent simulations of vicariance arising from the Last Glacial Maximum. We then weighed the relative contribution of distance versus environmental or geographic barriers to pairwise Φ ST with a distance‐based redundancy analysis (dbRDA). Results We observed a diversity of outcomes, although the majority of species fit a few broad biogeographic regions. Repeated coalescent simulation of a simple vicariance model yielded a wide distribution of pairwise Φ ST that was very similar to empirical distributions observed across five putative barriers to gene flow. Three of these barriers had median Φ ST that were significantly larger than random expectation. Only 21 of 52 species analysed with dbRDA rejected the null model. Among these, 15 had overwater distance as a significant predictor of pairwise Φ ST , while 11 were significant for geographic or environmental barriers other than distance. Main conclusions Although there is support for three previously described barriers, phylogeographic discordance in the Indo‐Pacific Ocean indicates incongruity between processes shaping the distributions of diversity at the species and population levels. Among the many possible causes of this incongruity, genetic drift provides the most compelling explanation: given massive effective population sizes of Indo‐Pacific species, even hard vicariance for tens of thousands of years can yield Φ ST values that range from 0 to nearly 0.5.

Discovery of Cucumis melo endornavirus by deep sequencing of human stool samples in Brazil - Antonio Charlys da Costa; Elcio Leal; Danielle Gill; Flavio Augusto de Pádua Milagres; Shirley Vasconcelos Komninakis; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Márcia Cristina Alves Brito Sayão Lobato; Rogério Togisaki das Chagas; Maria de Fátima Neves dos Santos Abrão; Cassia Vitória de Deus Alves Soares; Xutao Deng; et al. (Virus Genes, 2019)

Pharmacological restoration of gut barrier function in stressed neonates partially reverses long-term alterations associated with maternal separation - Marion Rincel; Maïwenn Olier; Amandine Minni; Camille Monchaux de Oliveira; Yann Matime; Eric Gaultier; Isabelle Grit; Jean-Christophe Helbling; Anna Maria Costa; Amandine Lépinay; Marie-Pierre Moisan; Sophie Layé; et al. (Psychopharmacology, 2019)

Collections of Mungbean [Vigna radiata) (L.) R. Wilczek] and urdbean [V. mungo (L.) Hepper] in Vavilov Institute (VIR): traits diversity and trends in the breeding process over the last 100 years - Marina Burlyaeva; Margarita Vishnyakova; Maria Gurkina; Konstanin Kozlov; Cheng-Ruei Lee; Chau-Ti Ting; Roland Schafleitner; Sergey Nuzhdin; Maria Samsonova; Eric von Wettberg (Genetic Resources and Crop Evolution, 2019)

Correction to: Effects of metaperiodate and urea solutions on the serological diagnosis of human sporotrichosis using an indirect ELISA test - Letícia Maria Leomil Coelho; Julianne Caravita Grisolia; Maria Lúcia; Míriam Boczar; Eric Batista Ferreira; Denismar Alves Nogueira; Jorge Kleber Chavasco; Zoilo Pires de Camargo; Leila Maria Lopes-Bezerra; Luiz Felipe Leomil Coelho; Luiz Cosme Cotta Malaquias (Brazilian Journal of Microbiology, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Contrasting olfactory responses of two egg parasitoids to buckwheat floral scent are reflected in field parasitism rates - Maria Cristina Foti; Ezio Peri; Eric Wajnberg; Stefano Colazza; Michael Rostás (Journal of Pest Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Freshwater eels: A symbol of the effects of global change - Hilaire Drouineau; Caroline Durif; Martin Castonguay; Maria Mateo; Eric Rochard; Guy Verreault; Kazuki Yokouchi; Patrick Lambert (Fish and Fisheries, 2018)
Temperate eels Anguilla anguilla (European eel), A. rostrata (American eel) and A. japonica (Japanese eel) are three catadromous species which have been declining since the 1970s/1980s despite their remarkable adaptive capacity. Because of their specific life cycles, which share distant oceanic spawning grounds and continental growth stage, eels are affected by five components of the global change: (a) climate change affecting larval survival and drift, (b) an increase in pollution leading to high levels of contamination exacerbated by their high lipid levels, (c) increasing fragmentation and habitat loss that reduce dramatically the amount of available habitats and induce increased spawner mortality, (d) the appearance of Anguillicola crassus a parasitic alien nematode that impairs spawning success, and (e) the impact of commercial and recreational fisheries for all life stages of eel. In this context, the rapid increases of pressures during the “Great Acceleration” have surpassed the adaptive capacity of eels. This illustrates that cumulative effects of global change can lead to the collapse of species, even in species that have amazingly high adaptive capacities.

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Molecular and morphological data from Thoosidae in favour of the creation of a new suborder of Tetractinellida - JosÉ Luis Carballo; Eric Bautista-Guerrero; Paco CÁrdenas; Jose Antonio Cruz-Barraza; Jose Maria Aguilar-Camacho (Systematics and Biodiversity, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Wuhan large pig roundworm virus identified in human feces in Brazil - Adriana Luchs; Elcio Leal; Shirley Vasconcelos Komninakis; Flavio Augusto de Pádua Milagres; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Danielle Elise Gill; Xutao Deng; Eric Delwart; Ester Cerdeira Sabino; Antonio Charlys da Costa (Virus Genes, 2018)

GR3027 reversal of neurosteroid-induced, GABA-A receptor-mediated inhibition of human brain function: an allopregnanolone challenge study - Maja Johansson; Maria Månsson; Lars-Eric Lins; Bruce Scharschmidt; Magnus Doverskog; Torbjörn Bäckström (Psychopharmacology, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

Susceptibility to Soman Toxicity and Efficacy of LY293558 Against Soman-Induced Seizures and Neuropathology in 10-Month-Old Male Rats - James P. Apland; Vassiliki Aroniadou-Anderjaska; Taiza H. Figueiredo; Eric M. Prager; Cara H. Olsen; Maria F. M. Braga (Neurotoxicity Research, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

An invasive insect herbivore disrupts plant volatile-mediated tritrophic signalling - Letizia Martorana; Maria Cristina Foti; Gabriele Rondoni; Eric Conti; Stefano Colazza; Ezio Peri (Journal of Pest Science, 2017)

Native egg parasitoids recorded from the invasive Halyomorpha halys successfully exploit volatiles emitted by the plant–herbivore complex - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Maria Cristina Foti; Ezio Peri; Lara Maistrello; Tim Haye; Eric Conti (Journal of Pest Science, 2017)

Subduction initiation and ophiolite crust: new insights from IODP drilling - Mark K. Reagan; Julian A. Pearce; Katerina Petronotis; Renat R. Almeev; Aaron J. Avery; Claire Carvallo; Timothy Chapman; Gail L. Christeson; Eric C. Ferré; Marguerite Godard; Daniel E. Heaton; Maria Kirchenbaur; et al. (International Geology Review, 2017)

The matrix effect: how agricultural matrices shape forest fragment structure and amphibian composition - Lucas Ferrante; Fabricio Beggiato Baccaro; Eric Batista Ferreira; Maria Fernanda de Oliveira Sampaio; Thays Santos; Rodrigo Cesário Justino; Ariadne Angulo (Journal of Biogeography, 2017)
Aim Habitat loss and fragmentation are considered the main drivers of species population declines and extinctions in the world. The large‐scale replacement of natural habitats with human‐modified habitats, such as the replacement of forests with agricultural and livestock farming areas, creates a scenario where natural habitat patches are immersed in an inhospitable land use matrix. We sought to evaluate how forest fragments (FFs) are influenced by the different surrounding landscape components, where we assessed how agricultural matrices that differ in structure and seasonality affect the structure of FFs and their amphibian assemblages. Location Atlantic Forest, Brazil. Methods Using diverse methods including satellite imagery, historical land use and field data, we evaluated the effects of representative agricultural matrices on the structure of FFs and their amphibian composition, species richness and abundance. Results Our results suggest that the structure of FFs and amphibian composition, species richness and individual abundance are intimately linked to the type of matrix and its proportion around FFs. The nature of the matrix is more likely to affect species richness, individual abundance and composition of amphibian assemblages than FF size, reducing the species‐area relationship in FFs. There is strong support for the hypothesis that certain agricultural matrices facilitate FF exposure to the elements and a decrease in forest integrity within the fragment, which is reflected in a loss of strict forest inhabitants. Those matrices that allow for a greater exposure of FFs also appear to favour their occupation by habitat generalists. Main conclusions Surrounding matrices affect the structure and dynamics of forest remnants and should therefore be considered in management plans of severely fragmented landscapes. The influence of the land matrix should be urgently assessed, as it has effects on species occurrences and distribution. This is especially relevant considering the increasing deforestation rates in biodiversity hotspots world‐wide.

Decrease in Adult Neurogenesis and Neuroinflammation Are Involved in Spatial Memory Impairment in the Streptozotocin-Induced Model of Sporadic Alzheimer’s Disease in Rats - Taysa Bervian Bassani; Jéssica M. Bonato; Meira M. F. Machado; Valentín Cóppola-Segovia; Eric L. R. Moura; Silvio M. Zanata; Rúbia M. M. W. Oliveira; Maria A. B. F. Vital (Molecular Neurobiology, 2017)

Syncopation affects free body-movement in musical groove - Maria A. G. Witek; Tudor Popescu; Eric F. Clarke; Mads Hansen; Ivana Konvalinka; Morten L. Kringelbach; Peter Vuust (Experimental Brain Research, 2017)

The effect of action observation/execution on mirror neuron system recruitment: an fMRI study in healthy individuals - Roberto Gatti; Maria A. Rocca; Silvia Fumagalli; Erik Cattrysse; Eric Kerckhofs; Andrea Falini; Massimo Filippi (Brain Imaging and Behavior, 2017)

Host status of wild roe deer in bovine tuberculosis endemic areas - Sébastien Lambert; Jean Hars; Edouard Réveillaud; Jean-Louis Moyen; Hélène Gares; Thomas Rambaud; Eric Gueneau; Eva Faure; Maria-Laura Boschiroli; Céline Richomme (European Journal of Wildlife Research, 2017)

The expression patterns of aquaporin 9, vacuolar H+-ATPase, and cytokeratin 5 in the epididymis of the common vampire bat - Mariana M. Castro; Bongki Kim; Eric Hill; Maria C. Q. Fialho; Luciano C. H. P. Puga; Mariella B. Freitas; Sylvie Breton; Mariana Machado-Neves (Histochemistry and Cell Biology, 2017)

Coastal evolution and sedimentary mobility of Brøgger Peninsula, northwest Spitsbergen - Marine Bourriquen; Agnès Baltzer; Denis Mercier; Jérôme Fournier; Laurent Pérez; Sylvain Haquin; Eric Bernard; Maria Jensen (Polar Biology, 2016)

Toward a Quality-Controlled and Accessible Pitzer Model for Seawater and Related Systems - David R. Turner; Eric P. Achterberg; Chen-Tung A. Chen; Simon L. Clegg; Vanessa Hatje; Maria T. Maldonado; Sylvia G. Sander; Constant M. G. van den Berg; Mona Wells (Frontiers in Marine Science, 2016)

Over What Area Did the Oil and Gas Spread During the 2010 Deepwater Horizon Oil Spill? - Tamay Özgökmen; Eric Chassignet; Clint Dawson; Dmitry Dukhovskoy; Gregg Jacobs; James Ledwell; Oscar Garcia-Pineda; Ian MadDonald; Steven Morey; Maria Olascoaga; Andrew Poje; Mark Reed; et al. (Oceanography, 2016)

Molecular and morphological differentiation of sympatric larvae of coral excavating sponges of genus Thoosa - Eric Bautista-Guerrero; José Luis Carballo; Jose Maria Aguilar-Camacho; Itzel Sifuentes-Romero (Zoomorphology, 2016)

Binding of phenothiazines into allosteric hydrophobic pocket of human thioredoxin 1 - Eric Allison Philot; David da Mata Lopes; Aryane Tofanello de Souza; Antônio Sérgio Kimus Braz; Iseli Lourenço Nantes; Tiago Rodrigues; David Perahia; Maria A. Miteva; Luis Paulo Barbour Scott (European Biophysics Journal, 2016)

The Effect of Age Correction on Multivariate Classification in Alzheimer’s Disease, with a Focus on the Characteristics of Incorrectly and Correctly Classified Subjects - Farshad Falahati; Daniel Ferreira; Hilkka Soininen; Patrizia Mecocci; Bruno Vellas; Magda Tsolaki; Iwona Kłoszewska; Simon Lovestone; Maria Eriksdotter; Lars-Olof Wahlund; Andrew Simmons; Eric Westman (Brain Topography, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The energy balance over land and oceans: an assessment based on direct observations and CMIP5 climate models - Martin Wild; Doris Folini; Maria Z. Hakuba; Christoph Schär; Sonia I. Seneviratne; Seiji Kato; David Rutan; Christof Ammann; Eric F. Wood; Gert König-Langlo (Climate Dynamics, 2015)

Grassland management intensification weakens the associations among the diversities of multiple plant and animal taxa - Pete Manning; Martin M. Gossner; Oliver Bossdorf; Eric Allan; Yuan-Ye Zhang; Daniel Prati; Nico Blüthgen; Steffen Boch; Stefan Böhm; Carmen Börschig; Norbert Hölzel; Kirsten Jung; et al. (Ecology, 2015)
Land‐use intensification is a key driver of biodiversity change. However, little is known about how it alters relationships between the diversities of different taxonomic groups, which are often correlated due to shared environmental drivers and trophic interactions. Using data from 150 grassland sites, we examined how land‐use intensification (increased fertilization, higher livestock densities, and increased mowing frequency) altered correlations between the species richness of 15 plant, invertebrate, and vertebrate taxa. We found that 54% of pairwise correlations between taxonomic groups were significant and positive among all grasslands, while only one was negative. Higher land‐use intensity substantially weakened these correlations (35% decrease in r and 43% fewer significant pairwise correlations at high intensity), a pattern which may emerge as a result of biodiversity declines and the breakdown of specialized relationships in these conditions. Nevertheless, some groups (Coleoptera, Heteroptera, Hymenoptera and Orthoptera) were consistently correlated with multidiversity, an aggregate measure of total biodiversity comprised of the standardized diversities of multiple taxa, at both high and low land‐use intensity. The form of intensification was also important; increased fertilization and mowing frequency typically weakened plant–plant and plant–primary consumer correlations, whereas grazing intensification did not. This may reflect decreased habitat heterogeneity under mowing and fertilization and increased habitat heterogeneity under grazing. While these results urge caution in using certain taxonomic groups to monitor impacts of agricultural management on biodiversity, they also suggest that the diversities of some groups are reasonably robust indicators of total biodiversity across a range of conditions.

Consensus Paper: The Role of the Cerebellum in Perceptual Processes - Oliver Baumann; Ronald J. Borra; James M. Bower; Kathleen E. Cullen; Christophe Habas; Richard B. Ivry; Maria Leggio; Jason B. Mattingley; Marco Molinari; Eric A. Moulton; Michael G. Paulin; Marina A. Pavlova; et al. (The Cerebellum, 2015)

Preliminary differences in peripheral immune markers and brain metabolites between fatigued and non-fatigued breast cancer survivors: a pilot study - Suzanna Maria Zick; Heather Zwickey; Lisa Wood; Bradley Foerster; Tohfa Khabir; Benjamin Wright; Eric Ichesco; Ananda Sen; Richard Edmund Harris (Brain Imaging and Behavior, 2014)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Comparative study of non-invasive methods for assessing Daphnia magna embryo toxicity - Matthew C. Stensberg; Michael Anthony Zeitchek; Kul Inn; Eric S. McLamore; D. Marshall Porterfield; Maria S. Sepúlveda (Environmental Science and Pollution Research, 2014)

Exposure to respirable dust and manganese and prevalence of airways symptoms, among Swedish mild steel welders in the manufacturing industry - Maria Hedmer; Jan-Eric Karlsson; Ulla Andersson; Helene Jacobsson; Jörn Nielsen; Håkan Tinnerberg (International Archives of Occupational and Environmental Health, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Fast demographic traits promote high diversification rates of Amazonian trees - Timothy R. Baker; R. Toby Pennington; Susana Magallon; Emanuel Gloor; William F. Laurance; Miguel Alexiades; Esteban Alvarez; Alejandro Araujo; Eric J. M. M. Arets; Gerardo Aymard; Atila Alves de Oliveira; Iêda Amaral; et al. (Ecology Letters, 2014)
The Amazon rain forest sustains the world's highest tree diversity, but it remains unclear why some clades of trees are hyperdiverse, whereas others are not. Using dated phylogenies, estimates of current species richness and trait and demographic data from a large network of forest plots, we show that fast demographic traits – short turnover times – are associated with high diversification rates across 51 clades of canopy trees. This relationship is robust to assuming that diversification rates are either constant or decline over time, and occurs in a wide range of Neotropical tree lineages. This finding reveals the crucial role of intrinsic, ecological variation among clades for understanding the origin of the remarkable diversity of Amazonian trees and forests.

Enhancing the relevance of Shared Socioeconomic Pathways for climate change impacts, adaptation and vulnerability research - Bas J. van Ruijven; Marc A. Levy; Arun Agrawal; Frank Biermann; Joern Birkmann; Timothy R. Carter; Kristie L. Ebi; Matthias Garschagen; Bryan Jones; Roger Jones; Eric Kemp-Benedict; Marcel Kok; et al. (Climatic Change, 2014)

Investigation of blood parasites of pygoscelid penguins at the King George and Elephant Islands, South Shetlands Archipelago, Antarctica - Ralph Eric Thijl Vanstreels; Flavia R. Miranda; Valeria Ruoppolo; Ana Olívia de Almeida Reis; Erli Schneider Costa; Adriana Rodrigues de Lira Pessôa; João Paulo Machado Torres; Larissa Schmauder Teixeira da Cunha; Roberta da Cruz Piuco; Victor Hugo Valiati; Daniel González-Acuña; Marcelo B. Labruna; et al. (Polar Biology, 2014)

Understanding the biology of ex vivo-expanded CD8 T cells for adoptive cell therapy: role of CD62L - C. Marcela Díaz-Montero; Abdel-Aziz Zidan; Maria F. Pallin; Vasileios Anagnostopoulos; Mohamed L. Salem; Eric Wieder; Krishna Komanduri; Alberto J. Montero; Mathias G. Lichtenheld (Immunologic Research, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Bovine tuberculosis in “Eurasian” badgers (Meles meles) in France - Ariane Payne; Maria Laura Boschiroli; Eric Gueneau; Jean Louis Moyen; Thomas Rambaud; Barbara Dufour; Emmanuelle Gilot-Fromont; Jean Hars (European Journal of Wildlife Research, 2013)

Dynamic Conservation of Forest Genetic Resources in 33 European Countries - FRANÇOIS LEFÈVRE; JARKKO KOSKELA; JASON HUBERT; HOJKA KRAIGHER; ROMAN LONGAUER; DITTE C. OLRIK; SILVIO SCHÜLER; MICHELE BOZZANO; PARASKEVI ALIZOTI; REMIGIJUS BAKYS; CATHLEEN BALDWIN; DALIBOR BALLIAN; et al. (Conservation Biology, 2013)
Dynamic conservation of forest genetic resources (FGR) means maintaining the genetic diversity of trees within an evolutionary process and allowing generation turnover in the forest. We assessed the network of forests areas managed for the dynamic conservation of FGR (conservation units) across Europe (33 countries). On the basis of information available in the European Information System on FGR (EUFGIS Portal), species distribution maps, and environmental stratification of the continent, we developed ecogeographic indicators, a marginality index, and demographic indicators to assess and monitor forest conservation efforts. The pan‐European network has 1967 conservation units, 2737 populations of target trees, and 86 species of target trees. We detected a poor coincidence between FGR conservation and other biodiversity conservation objectives within this network. We identified 2 complementary strategies: a species‐oriented strategy in which national conservation networks are specifically designed for key target species and a site‐oriented strategy in which multiple‐target units include so‐called secondary species conserved within a few sites. The network is highly unbalanced in terms of species representation, and 7 key target species are conserved in 60% of the conservation units. We performed specific gap analyses for 11 tree species, including assessment of ecogeographic, demographic, and genetic criteria. For each species, we identified gaps, particularly in the marginal parts of their distribution range, and found multiple redundant conservation units in other areas. The Mediterranean forests and to a lesser extent the boreal forests are underrepresented. Monitoring the conservation efficiency of each unit remains challenging; however, Conservación Dinámica de Recursos Genéticos Forestales en 33 Países Europeos

Spatial and temporal development of phytoplankton iron stress in relation to bloom dynamics in the high‐latitude North Atlantic Ocean - Thomas J. Ryan-Keogh; Anna I. Macey; Maria C. Nielsdóttir; Michael I. Lucas; Sebastian S. Steigenberger; Mark C. Stinchcombe; Eric P. Achterberg; Thomas S. Bibby; C. Mark Moore (Limnology and Oceanography, 2013)
The high‐latitude North Atlantic (HLNA) is characterized by a marked seasonal phytoplankton bloom, which removes the majority of surface macronutrients. However, incomplete nitrate depletion is frequently observed during summer in the region, potentially reflecting the seasonal development of an iron (Fe) limited phytoplankton community. In order to investigate the seasonal development and spatial extent of iron stress in the HLNA, nutrient addition experiments were performed during the spring (May) and late summer (July and August) of 2010. Grow‐out experiments (48–120 h) confirmed the potential for iron limitation in the region. Short‐term (24 h) incubations further enabled high spatial coverage and mapping of phytoplankton physiological responses to iron addition. The difference in the apparent maximal photochemical yield of photosystem II (PSII) (F v : F m ) between nutrient (iron) amended and control treatments (Δ(F v : F m )) was used as a measure of the relative degree of iron stress. The combined observations indicated variability in the seasonal cycle of iron stress between different regions of the Irminger and Iceland Basins of the HLNA, related to the timing of the annual bloom cycle in contrasting biogeochemical provinces. Phytoplankton iron stress developed during the transition from the prebloom to peak bloom conditions in the HLNA and was more severe for larger cells. Subsequently, iron stress was reduced in regions where macronutrients were depleted following the bloom. Iron availability plays a significant role in the biogeochemistry of the HLNA, potentially lowering the efficiency of one of the strongest biological carbon pumps in the ocean.

Several enteropathogens are circulating in suckling and newly weaned piglets suffering from diarrhea in the province of Villa Clara, Cuba - Pedro Yoelvys de la Fé Rodríguez; Luis O. Maroto Martin; Eduardo Cruz Muñoz; Hein Imberechts; Patrick Butaye; Bruno Maria Goddeeris; Eric Cox (Tropical Animal Health and Production, 2013)

Amyloid-β metabolism in Niemann-Pick C disease models and patients - Niklas Mattsson; Maria Olsson; Mikael K. Gustavsson; Marko Kosicek; Martina Malnar; Jan-Eric Månsson; Maria Blomqvist; Johan Gobom; Ulf Andreasson; Gunnar Brinkmalm; Charles Vite; Silva Hecimovic; et al. (Metabolic Brain Disease, 2012)

Uptake of copper from plasma proteins in cells where expression of CTR1 has been modulated - Theodros Z. Kidane; Ramin Farhad; Kyoung Jin Lee; Abraham Santos; Eric Russo; Maria C. Linder (BioMetals, 2012)

Pathogens as potential hitchhikers on intercontinental dust - Ilka Toepfer; Jocelyne Favet; Anette Schulte; Maria Schmölling; Werner Butte; Eric W. Triplett; William J. Broughton; Anna A. Gorbushina (Aerobiologia, 2012)

Toll-like receptor-2 and interleukin-6 mediate cardiomyocyte protection from apoptosis during Trypanosoma cruzi murine infection - Nicolás Eric Ponce; Roxana Carolina Cano; Eugenio Antonio Carrera-Silva; Ana Paula Lima; Susana Gea; Maria Pilar Aoki (Medical Microbiology and Immunology, 2012)

Lack of ceruloplasmin expression alters aspects of copper transport to the fetus and newborn, as determined in mice - Yu-Ling Chu; Eric N. Sauble; Anthony Cabrera; Aleeza Roth; M. Leigh Ackland; Julian F. B. Mercer; Maria C. Linder (BioMetals, 2012)

Human metapneumovirus strains circulating in Latin America - Josefina Garcia; Merly Sovero; Tadeusz Kochel; V. Alberto Laguna-Torres; Maria Ester Gamero; Jorge Gomez; Felix Sanchez; Ana E. Arango; Sergio Jaramillo; Eric S. Halsey (Archives of Virology, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Modeling habituation in rat EEG-evoked responses via a neural mass model with feedback - Srinivas Laxminarayan; Gilead Tadmor; Solomon G. Diamond; Eric Miller; Maria Angela Franceschini; Dana H. Brooks (Biological Cybernetics, 2011)

Evolutionary significance of an algal gene encoding an [FeFe]-hydrogenase with F-domain homology and hydrogenase activity in Chlorella variabilis NC64A - Jonathan E. Meuser; Eric S. Boyd; Gennady Ananyev; Devin Karns; Randor Radakovits; U. M. Narayana Murthy; Maria L. Ghirardi; G. Charles Dismukes; John W. Peters; Matthew C. Posewitz (Planta, 2011)

High prevalence of F4+ and F18+ Escherichia coli in Cuban piggeries as determined by serological survey - Pedro Yoelvys de la Fé Rodríguez; Annelies Coddens; Emanuele Del Fava; José Cortiñas Abrahantes; Ziv Shkedy; Luis O. Maroto Martin; Eduardo Cruz Muñoz; Luc Duchateau; Eric Cox; Bruno Maria Goddeeris (Tropical Animal Health and Production, 2011)

Important Factors in the Size Reduction of Polymer-Stabilized Drug Particle Suspensions Using High-Pressure Homogenization - Francis S. Romanski; Eric Jayjock; Fernando J. Muzzio; Maria Silvina Tomassone (Journal of Pharmaceutical Innovation, 2011)

The timing of sea ice formation and exposure to photosynthetically active radiation along the Western Antarctic Peninsula - Christian H. Fritsen; Jeramie C. Memmott; Robin M. Ross; Langdon B. Quetin; Maria Vernet; Eric D. Wirthlin (Polar Biology, 2011)

Microsatellite analysis supports mitochondrial phylogeography of the hellbender (Cryptobranchus alleganiensis) - Maria Tonione; Jarrett R. Johnson; Eric J. Routman (Genetica, 2011)

Matrix metalloprotease-3 and tissue inhibitor of metalloprotease-1 mRNA and protein levels are altered in response to traumatic skeletal muscle injury - Maria L. Urso; Eric R. Szelenyi; Gordon L. Warren; Brian R. Barnes (European Journal of Applied Physiology, 2010)

Age-dependent cognitive impairment in a Drosophila Fragile X model and its pharmacological rescue - Catherine H. Choi; Sean M. J. McBride; Brian P. Schoenfeld; David A. Liebelt; David Ferreiro; Neal J. Ferrick; Paul Hinchey; Maria Kollaros; Rebecca L. Rudominer; Allison M. Terlizzi; Eric Koenigsberg; Yan Wang; et al. (Biogerontology, 2010)

Characterization of HIV-1 RNA forms in the plasma of patients undergoing successful HAART - Carlos A. Lopez; Manuel Vazquez; Martin D. Hill; Maria Del C. Colon; Tirtsa Porrata-Doria; Ian C. D. Johnston; Eric Lorenzo (Archives of Virology, 2010)

Annotation and overview of the Pseudomonas savastanoi pv. savastanoi NCPPB 3335 draft genome reveals the virulence gene complement of a tumour‐inducing pathogen of woody hosts - Pablo Rodríguez‐Palenzuela; Isabel M. Matas; Jesús Murillo; Emilia López‐Solanilla; Leire Bardaji; Isabel Pérez‐Martínez; Martín E. Rodríguez‐Moskera; Ramón Penyalver; Maria M. López; José M. Quesada; Bryan S. Biehl; Nicole T. Perna; et al. (Environmental Microbiology, 2010)
Summary Pseudomonas savastanoi pv. savastanoi is a tumour‐inducing pathogen of Olea europaea L. causing olive knot disease. Bioinformatic analysis of the draft genome sequence of strain NCPPB 3335, which encodes 5232 predicted coding genes on a total length of 5856 998 bp and a 57.12% G + C, revealed a large degree of conservation with Pseudomonas syringae pv. phaseolicola 1448A and P. syringae pv. tabaci 11528. However, NCPPB 3335 contains twelve variable genomic regions, which are absent in all previously sequenced P. syringae strains. Various features that could contribute to the ability of this strain to survive in a woody host were identified, including broad catabolic and transport capabilities for degrading plant‐derived aromatic compounds, the duplication of sequences related to the biosynthesis of the phytohormone indoleacetic acid ( iaaM, iaaH ) and its amino acid conjugate indoleacetic acid‐lysine ( iaaL gene), and the repertoire of strain‐specific putative type III secretion system effectors. Access to this seventh genome sequence belonging to the ‘ P. syringae complex’ allowed us to identify 73 predicted coding genes that are NCPPB 3335‐specific. Results shown here provide the basis for detailed functional analysis of a tumour‐inducing pathogen of woody hosts and for the study of specific adaptations of a P. savastanoi pathovar.

Arsenic in the Hair of the Individuals in Santana-AP-Brazil: Significance of Residence Location - Simone de Fátima Pinheiro Pereira; Augusto Fonseca Saraiva; Maria Izabel Fernandes de Alencar; Stephen Eric Ronan; Wagner Soares de Alencar; Geiso Rafael Fonseca Oliveira; Cleber Silva e Silva; Rafaella Galvão Miranda (Bulletin of Environmental Contamination and Toxicology, 2010)

Two Italian Families with ITPR1 Gene Deletion Presenting a Broader Phenotype of SCA15 - Eleonora Di Gregorio; Laura Orsi; Massimiliano Godani; Giovanna Vaula; Stella Jensen; Eric Salmon; Giancarlo Ferrari; Stefania Squadrone; Maria Cesarina Abete; Claudia Cagnoli; Alessandro Brussino; Alfredo Brusco (The Cerebellum, 2010)

Role of the cAMP-binding protein Epac in cardiovascular physiology and pathophysiology - Mélanie Métrich; Magali Berthouze; Eric Morel; Bertrand Crozatier; Ana Maria Gomez; Frank Lezoualc’h (Pflügers Archiv - European Journal of Physiology, 2010)

Assessment of the effects of physical training in patients with chronic heart failure: the utility of effort-independent exercise variables - Hareld M. C. Kemps; Wouter R. de Vries; Sandor L. Schmikli; Maria L. Zonderland; Adwin R. Hoogeveen; Eric J. M. Thijssen; Goof Schep (European Journal of Applied Physiology, 2010)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Co-localization of hyperphosphorylated tau and caspases in the brainstem of Alzheimer’s disease patients - Maria Sen Mun Wai; Yong Liang; Chun Shi; Eric Y. P. Cho; Hsiang-fu Kung; David T. Yew (Biogerontology, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Leaf traits capture the effects of land use changes and climate on litter decomposability of grasslands across Europe - Claire Fortunel; Eric Garnier; Richard Joffre; Elena Kazakou; Helen Quested; Karl Grigulis; Sandra Lavorel; Pauline Ansquer; Helena Castro; Pablo Cruz; JiŘí DoleŽal; Ove Eriksson; et al. (Ecology, 2009)
Land use and climate changes induce shifts in plant functional diversity and community structure, thereby modifying ecosystem processes. This is particularly true for litter decomposition, an essential process in the biogeochemical cycles of carbon and nutrients. In this study, we asked whether changes in functional traits of living leaves in response to changes in land use and climate were related to rates of litter potential decomposition, hereafter denoted litter decomposability, across a range of 10 contrasting sites. To disentangle the different control factors on litter decomposition, we conducted a microcosm experiment to determine the decomposability under standard conditions of litters collected in herbaceous communities from Europe and Israel. We tested how environmental factors (disturbance and climate) affected functional traits of living leaves and how these traits then modified litter quality and subsequent litter decomposability. Litter decomposability appeared proximately linked to initial litter quality, with particularly clear negative correlations with lignin‐dependent indices (litter lignin concentration, lignin : nitrogen ratio, and fiber component). Litter quality was directly related to community‐weighted mean traits. Lignin‐dependent indices of litter quality were positively correlated with community‐weighted mean leaf dry matter content (LDMC), and negatively correlated with community‐weighted mean leaf nitrogen concentration (LNC). Consequently, litter decomposability was correlated negatively with community‐weighted mean LDMC, and positively with community‐weighted mean LNC. Environmental factors (disturbance and climate) influenced community‐weighted mean traits. Plant communities experiencing less frequent or less intense disturbance exhibited higher community‐weighted mean LDMC, and therefore higher litter lignin content and slower litter decomposability. LDMC therefore appears as a powerful marker of both changes in land use and of the pace of nutrient cycling across 10 contrasting sites.

RO4938581, a novel cognitive enhancer acting at GABAA α5 subunit-containing receptors - Theresa M. Ballard; Frédéric Knoflach; Eric Prinssen; Edilio Borroni; Jeffrey A. Vivian; Jennifer Basile; Rodolfo Gasser; Jean-Luc Moreau; Joseph G. Wettstein; Bernd Buettelmann; Henner Knust; Andrew W. Thomas; et al. (Psychopharmacology, 2009)

Copper binding components of blood plasma and organs, and their responses to influx of large doses of 65Cu, in the mouse - Anthony Cabrera; Erin Alonzo; Eric Sauble; Yu Ling Chu; Dionne Nguyen; Maria C. Linder; Dee S. Sato; Andrew Z. Mason (BioMetals, 2008)

Differential infant carrying in captive and wild common marmosets (Callithrix jacchus) - Maria Emilia Yamamoto; Fabíola S. Albuquerque; Nívia A. Lopes; Eric S. Ferreira (acta ethologica, 2008)

An integrated greenhouse gas assessment of an alternative to slash‐and‐burn agriculture in eastern Amazonia - ERIC A. DAVIDSON; TATIANA DEANE De ABREU SÁ; CLAUDIO J. REIS CARVALHO; RICARDO De OLIVEIRA FIGUEIREDO; MARIA do SOCORRO A. KATO; OSVALDO R. KATO; FRANÇOISE YOKO ISHIDA (Global Change Biology, 2008)
Fires set for slash‐and‐burn agriculture contribute to the current unsustainable accumulation of atmospheric greenhouse gases, and they also deplete the soil of essential nutrients, which compromises agricultural sustainability at local scales. Integrated assessments of greenhouse gas emissions have compared intensive cropping systems in industrialized countries, but such assessments have not been applied to common cropping systems of smallholder farmers in developing countries. We report an integrated assessment of greenhouse gas emissions in slash‐and‐burn agriculture and an alternative chop‐and‐mulch system in the Amazon Basin. The soil consumed atmospheric methane (CH 4 ) under slash‐and‐burn treatment and became a net emitter of CH 4 to the atmosphere under the mulch treatment. Mulching also caused about a 50% increase in soil emissions of nitric oxide and nitrous oxide and required greater use of fertilizer and fuel for farm machinery. Despite these significantly higher emissions of greenhouse gases during the cropping phase under the alternative chop‐and‐mulch system, calculated pyrogenic emissions in the slash‐and‐burn system were much larger, especially for CH 4 . The global warming potential CO 2 ‐equivalent emissions calculated for the entire crop cycles were at least five times lower in chop‐and‐mulch compared with slash‐and‐burn. The crop yields were similar for the two systems. While economic and logistical considerations remain to be worked out for alternatives to slash‐and‐burn, these results demonstrate a potential ‘win‐win’ strategy for maintaining soil fertility and reducing net greenhouse gas emissions, thus simultaneously contributing to sustainability at both spatial scales.

Comparative ecology of the European eel, Anguilla anguilla (L., 1758), in a large Iberian river - José Lino Costa; Isabel Domingos; Carlos A. Assis; Pedro R. Almeida; Francisco Moreira; Eric Feunteun; Maria José Costa (Environmental Biology of Fishes, 2008)

Neuroprotective Role of Antidiabetic Drug Metformin Against Apoptotic Cell Death in Primary Cortical Neurons - Mohamad-Yehia El-Mir; Dominique Detaille; Gloria R-Villanueva; Maria Delgado-Esteban; Bruno Guigas; Stephane Attia; Eric Fontaine; Angeles Almeida; Xavier Leverve (Journal of Molecular Neuroscience, 2008)

Reproducibility of onset and recovery oxygen uptake kinetics in moderately impaired patients with chronic heart failure - Hareld M. C. Kemps; Wouter R. De Vries; Adwin R. Hoogeveen; Maria L. Zonderland; Eric J. M. Thijssen; Goof Schep (European Journal of Applied Physiology, 2007)

Helicobacter pylori SabA adhesin evokes a strong inflammatory response in human neutrophils which is down-regulated by the neutrophil-activating protein - Christoffer Petersson; Maria Forsberg; Marina Aspholm; Farzad O. Olfat; Tony Forslund; Thomas Borén; Karl-Eric Magnusson (Medical Microbiology and Immunology, 2006)

The thiol-disulfide oxidoreductase system in the cold-adapted bacterium Pseudoalteromonas haloplanktis TAC 125: discovery of a novel disulfide oxidoreductase enzyme - Stefania Madonna; Rosanna Papa; Leila Birolo; Flavia Autore; Nunzianna Doti; Gennaro Marino; Eric Quemeneur; Giovanni Sannia; Maria L. Tutino; Angela Duilio (Extremophiles, 2006)

Catecholase activity of a μ-hydroxodicopper(II) macrocyclic complex: structures, intermediates and reaction mechanism - Iryna A. Koval; Catherine Belle; Katalin Selmeczi; Christian Philouze; Eric Saint-Aman; Anna Maria Schuitema; Patrick Gamez; Jean-Louis Pierre; Jan Reedijk (JBIC Journal of Biological Inorganic Chemistry, 2005)

Effects of An E-cadherin-Derived Peptide on the Gene Expression of Caco-2 Cells - Anna Maria Calcagno; Jennifer M. Fostel; Eric L. Reyner; Ernawati Sinaga; James T. Alston; William B. Mattes; Teruna J. Siahaan; Joseph A. Ware (Pharmaceutical Research, 2004)

Sulfatide is associated with insulin granules and located to microdomains of a cultured beta cell line - Maria Blomqvist; Thomas Osterbye; Jan-Eric Månsson; Thomas Horn; Karsten Buschard; Pam Fredman (Glycoconjugate Journal, 2002)

Distribution of HERV-LTR elements in the 5′-flanking region of HLA-DQB1 and association with autoimmunity - Maria Pascual; Javier Martin; Antonio Nieto; Marius J. Giphart; Arno R. van der Slik; René R.P. de Vries; Eric Zanelli (Immunogenetics, 2001)

Isolation and Characterization by Direct Amplification of Length Polymorphisms (DALP) of Codominant Genetic Markers with Mendelian Inheritance in Neoseiulus Californicus (Acari: Phytoseiidae) - Marie-Jeanne Perrot-Minnot; Jacques Lagnel; Eric Desmarais; Maria Navajas (Experimental and Applied Acarology, 2000)

Multiple-input, multiple-output system identification for characterization of limb stiffness dynamics - Eric J. Perreault; Robert F. Kirsch; Ana Maria Acosta (Biological Cybernetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Supersquirt: Dynamics of the Gulf of Tehuantepec, Mexico - Eric Barton; Maria Argote; Juan Brown; Michael Kosro; Miguel Lavin; Jose Robles; Robert Smith; Armando Trasvina; Hector Velez (Oceanography, 1993)